Elective Surgery System Strengthening: Development, Measurement, and Validation of the Surgical Preparedness Index Across 1632 Hospitals in 119 Countries - James C Glasbey; Ruhi Fadzlyana Jailani; Razrim Rahim (The Lancet, 2024)
NIHR Global Health Unit on Global Surgery , COVIDSurg Collaborative [James C Glasbey, Tom EF Abbott, Adesoji Ademuyiwa, Adewale Adisa, Ehab AlAmeer, Sattar Alshryda, Alexis P Arnaud, Brittany Bankhead-Kendall, M K Abou Chaar, Daoud Chaudhry, Ainhoa Costas-Chavarri, Miguel F Cunha, Justine I Davies, Anant Desai, Muhammed Elhadi, Marco Fiore, James Edward Fitzgerald, Maria Fourtounas, Alex James Fowler, Kay Futaba, Gaetano Gallo, Dhruva Ghosh, Rohan R Gujjuri, Rebecca Hamilton, Parvez Haque, Ewen M Harrison, Peter Hutchinson, Gabriella Hyman, Arda Isik, Umesh Jayarajah, Haytham MA Kaafarani, Bryar Kadir, Ismail Lawani, Hans Lederhuber, Elizabeth Li, Markus W Löffler, Maria Aguilera Lorena, Harvinder Mann, Janet Martin, Dennis Mazingi, Craig D McClain, Kenneth A McLean, John G Meara, Antonio Ramos-De La Medina, Mengistu Mengesha, Ana Minaya, Maria Marta Modolo, Rachel Moore, Dion Morton, Dmitri Nepogodiev, Faustin Ntirenganya, Francesco Pata, Rupert Pearse, Maria Picciochi, Thomas Pinkney, Peter Pockney, Gabrielle H van Ramshorst, Toby Richards, April Camilla Roslani, Sohei Satoi, Raza Sayyed, Richard Shaw, Joana FF Simões, Neil Smart, Richard Sullivan, Malin Sund, Sudha Sundar, Stephen Tabiri, Elliott H Taylor, Mary L Venn, Dakshitha Wickramasinghe, Naomi Wright, Sebastian Bernardo Shu Yip, Aneel Bhangu, Omar Omar, Ewen Harrison, Aneel A Bhangu, Kwabena Siaw-Acheampong, Ruth A Benson, Edward Bywater, Brett E Dawson, Jonathan P Evans, Emily Heritage, Conor S Jones, Sivesh K Kamarajah, Chetan Khatri, Rachel A Khaw, James M Keatley, Andrew Knight, Samuel Lawday, Harvinder S Mann, Ella J Marson, Siobhan C Mckay, Emily C Mills, Gianluca Pellino, Abhinav Tiwari, Isobel M Trout, Richard JW Wilkin, Sadi Abukhalaf, Michel Adamina, Adesoji O Ademuyiwa, Arnav Agarwal, Murat Akkulak, Ehab Alameer, Derek Alderson, Felix Alakaloko, Markus Albertsmeier, Osaid Alser, Muhammad Alshaar, Knut Magne Augestad, Faris Ayasra, José Azevedo, Brittany K Bankhead-Kendall, Emma Barlow, David Beard, Ruth Blanco-Colino, Amanpreet Brar, Ana Minaya-Bravo, Kerry A Breen, Chris Bretherton, Igor Lima Buarque, Joshua Burke, Edward J Caruana, Mohammad Chaar, Sohini Chakrabortee, Peter Christensen, Daniel Cox, Moises Cukier, Giana H Davidson, Salomone Di Saverio, Thomas M Drake, John G Edwards, Sameh Emile, Shebani Farik, Samuel Ford, Tatiana Garmanova, Gustavo Mendonça Ataíde Gomes, Gustavo Grecinos, Ewen A Griffiths, Magdalena Gruendl, Constantine Halkias, Intisar Hisham, Peter J Hutchinson, Shelley Hwang, Michael D Jenkinson, Pascal Jonker, Debby Keller, Angelos Kolias, Schelto Kruijff, Sezai Leventoglu, Andrey Litvin, Andrew Loehrer, Maria Marta Modolo, Piotr Major, Hassan N Mashbari, Symeon Metallidis, Helen M Mohan, David Moszkowicz, Susan Moug, Joshua S Ng-Kamstra, Mayaba Maimbo, Ionut Negoi, Milagros Niquen, Maricarmen Olivos, Kacimi Oussama, Oumaima Outani, Marie Dione Parreno-Sacdalanm, Carlos Jose Perez Rivera, Thomas D Pinkney, Willemijn van der Plas, Ahmad Qureshi, Dejan Radenkovic, Antonio Ramos-De La Medina, Elliot J Revell, Keith Roberts, April C Roslani, Martin Rutegård, Juan José Segura-Sampedro, Irène Santos, Andrew Schache, Andreas A Schnitzbauer, Justina O Seyi-Olajide, Neil Sharma, Catherine A Shaw, Sebastian Shu, Kjetil Soreide, Antonino Spinelli, Grant D Stewart, Philip Townend, Georgios Tsoulfas, Raghavan Vidya, Dale Vimalachandran, Oliver J Warren, Duane Wedderburn, NA EuroSurg, NA European Society of Coloproctology (ESCP), NA Global Initiative for Children's Surgery, NA GlobalSurg, NA GlobalPaedSurg, NA ItSURG, NA PTSurg, NA SpainSurg, NA Italian Society of Colorectal Surgery, NA Association of Surgeons in Training, NA Irish Surgical Research Collaborative (ISRC), NA Transatlantic Australasian Retroperitoneal Sarcoma Working, NA Italian Society of Surgical Oncology, Lesley Booth, Margaret Barker, Neil Barker, Shirley Cooke, Suzanne Doré, Nigel Horwood, Emmy Runigamugabo, Carrie Tierney Weir, Mike Bahrami-Hessari, Asad Riaz, Jaffer Shah, Mohammed Safi, Dariel Thereska, Irida Dajti, Riadh Cheddadi, Anisse Tidjane, Carlos A Quinteros, Ahmed khelfaoui, Khalifa M Salem, Omar Riffi, Salah Eddine O Kacimi, Salim Loudjedi, Tidjani Damerdji, Diana A Pantoja Pachajoa, René M Palacios Huatuco, Fernando A Alvarez, Alejandro M Doniquian, Roberto A Abeldaño Zuñiga, Francisco Schlottmann, Carlos M Cobos, Cecilia Gigena, Agustin Albani Forneris, Agustin Duro, Agustín M García-Mansilla, Virginia Cano Busnelli, Catalina Poggi, Pedro L Mercado, Marcos González, Agustina F Castro Lalin, Horacio F Mayer, Rodrigo Brandariz, Pablo A Slullitel, Rocio Boudou, Pablo A Lobos, María C Uffelmann, Maria L Petersen, Emilia Luzzi, Fernando L Padilla Lichtenberger, María S Crespi Amor, Celeste S Zarratea, Tomas A Esteves, Nicolas A Gemelli, Sebastián Tirapegui, Juan Liyo, Jordán Scherñuk, Luis A Boccalatte, Ruben D Balmaceda, Jose L D'Addino, María M Caubet, José A Calderón Arancibia, Carina Chwat, Brian Morris, Nicolas Avellaneda, Ivana I Pedraza Salazar, Diego G Eskinazi, Lara Vargas, María E Muriel, Sergio M Lucchini, Martijn P Gosselink, Amelia L Davis, John C Barker, Kirby R Qin, David M Proud, Daniel RA Cox, Su Kah Goh, David S Liu, Damien M Wu, Neil D Merrett, Sarit S Badiani, Shomik Sengupta, Anshini Jain, Christopher J Steen, Enoch Wong, Christopher CK Ip, Matthew G Leaning, Conor B McCartney, Sivakumar Gananadha, Evie FW Yeap, Sean G Stevens, Anh N Vu, Sarah A Martin, Guy H M Stanley, David I Watson, Philip J Townend, Thomas K Young, Georgia T Cox, Amanda C Dawson, Sharon E Laura, Elizabeth W Y Lun, Ina X Liang, Christine J O'Neill, Natalie J Lott, Alwin Chuan, SK Saravanan, Justin Gundara, Bee Shan Ong, Ramesh M Nataraja, Maurizio Pacilli, Daniel M Foley, Geraldine J Ooi, Luke Traeger, Ewan MacDermid, Jurstine Daruwalla, Russell Hodgson, Alexander G Heriot, Christopher S Mulligan, Nicholas D A Blefari, Shaun S Purcell, Adam J Frankel, Glen R Guerra, Joan S Tefay, Rhea W Y Liang, Hidde M Kroon, Anthony W Farfus, Leigh R Warren, Jennifer M Roy, Robert J Whitfield, Cea-Cea B Moller, Sean S Davis, Tarik Sammour, Yick Ho Lam, Kevin Kour, Siang Wei Gan, Brendon J Coventry, Joseph A Dawson, Martin D Batstone, Sebastian K King, Nathan J Scott, Jonathan W Foo, Talia Shepherd, Richard S Page, Peter F Choong, Henry E Badgery, Lynn Chong, Lillian Taylor, Michael W Hii, Gavin M Wright, Joseph CH Kong, Matthew M Watson, Jacob Bock, Surjit S Lidder, Patrick Elias, Sathisvaran Kanavathy, Cherry E Koh, Srinivas Kondalsamy Chennakesavan, Vishwakar Panuganti, Haider Latif, Justin MC Yeung, Alex J Besson, Eunice Q Y Tse, Meron E Pitcher, Danielle L Taylor, Christopher B Nahm, Alicia Lim, Kevin Tree, Felix Aigner, Christopher Dawoud, Philipp Foessleitner, Matthias Zimmermann, Dominik Wiedemann, Oliver Findl, Franka Messner, Marlies Bauer, Felix Nägele, Irmgard E Kronberger, Dietmar Öfner, Bettina Härter, Nina Ru B Bicz, Paul M Zwittag, Nikolaus Poier, Francisco Ruiz Navarro, Yorck A Zebuhr, Paul Köglberger, Clemens G Wiesinger, Erwin Mathew, Felipe Trivik-Barrientos, Ingmar Königsrainer, Gabriel Djedovic, Tina U Cohnert, David B Lumenta, Georg Singer, Andreas Leithner, Lars-Peter Kamolz, Alexandros Andrianakis, Paul Puchwein, Saulius Mikalauskas, Patrick Kirchweger, Reinhold Függer, Christof Mittermair, Elisabeth Russe, Peter Paal, Martin Grünbart, Michael de Cillia, Helmut G Weiss, Florian Steiner, Alf Dorian Binder, Elgun Samadov, Arturan Ibrahimli, Gurbankhan Muslumov, Nuru Y Bayramov, Jada M Saunders, Noora Almoosa, Huzifa Haj-Ibrahim, Martin Maresch, Weaam K Ezzdean, Isam M Juma, Layla H Hasan, Fayza HA Haider, Ghassan Salman Alfaqawi, Mohammed S Alam, Shahnoor Islam, AKM K Basher, Ashrarur Rahman Mitul, Nazmul Islam, Antje E Oosterkamp, Tanveer Ahmed, M Jafrul Hannan, Greg M Padmore, Alex F Doyle, Karisha L LaCorbiniere, Rico D R Boyce, Paul T Ragoobar, Keisha M Y Walkes, Amelia A Haynes, Sasha M Corbin, Yauheniya A Litvina, Anvar Makhmudov, Sébastien Strypstein, Bert Dhondt, Ricky Rasschaert, Yasser Farid, El Mahdi Wahib, Manon Pigeolet, Koen Van Belle, Stefan De Wachter, Niels Komen, Mathieu PJ Vandeputte, Gabrielle H van Ramshorst, Yanina JL Jansen, Jasper Stijns, Jef Van den Eynde, Benedicte I Olowo, Israel C Feraudy, Vedran Dragisic, Vlatka Martinovic, Tatjana Barišić, Nikolina Penava, Igor Hudic, Samir Delibegovic, Gordana Bogdanović, Gordana Grgić, Anis Cerovac, Elmedina Cerovac, Alemayehu G Bedada, Glauco Baiocchi, Alberto Wainstein, Elaine Christine D Moisés, Ana Carolina Tagliatti Zani, Caio Antonio de Campos Prado, Carolina Panis, Daniel Rech, Ruan Gabriel Soares da Silva, Edwaldo E Joviliano, Ricardo F Rezende, Igor G N Reis, Robinson E S Pires, Adriana Borgonovi Christiano, Heitor F X Consani, Felipe G Pugliesi, Flavio R Takeda, Alessandro W Mariani, Ricardo J B Valadares, Nelson A Andreollo, Luiz Roberto Lopes, Cristiano Tonello, Nivaldo Alonso, Carlos Ferreira dos Santos, Leonardo S Lima, Wilson Salgado, Thiago H S Pereira, Arthur Paredes Gatti, Ramon N L Oliva, Caroline N Nardi, Alvaro F L Sousa, Ivonizete P Ribeiro, Herica E F Carvalho, Layze B Oliveira, Guilherme Schneider, William Augusto Casteleins, Larissa M Silva, Carlos Augusto Gomes, Alonço da Cunha Viana Júnior, Ricardo P Cruz, Gustavo MA Gomes, Igor L Buarque, Aldo V Barros, Gustavo B Marangon, Ronald LG Flumignan, Luís CU Nakano, Patrícia IF Pascoal, Brena C Santos, Danielle AB Kuramoto, Rebeca M Correia, Fabio CF Amaral, Carolina DQ Flumignan, Jairo A Dussán-Sarria, Romeo L Simões, William Augusto Casteleins, Robson L Amorim, Jeancarllo S Silva, Humberto F Lyra Junior, Nathalia S Julio, Marlus T Gerber, José Mauro dos Santos, Joao Carlos C de Oliveira, Camila VC Palamim, Fernando AL Marson, Iolanda M Gomes, Priscila R Oliveira, Ana Lucia L M Lima, Vladimir C Carvalho, Jorge S Silva, Ulysses Ribeiro NA, Gustavo Andreazza Laporte, Mateus Capuzzo Gonçalves, Lais S Botacin, Melissa AG Avelino, Luiz Gustavo O Brito, Evguenia T Hristova, Vladislav Valentinov Stoyanov, Boris E Sakakushev, Dragomir D Dardanov, Manol B Sokolov, Ananya Mehta, Elitsa H Gyokova, Mohamed Abdullahi, Martin P Karamanliev, Dobromir D Dimitrov, Mihail T Slavchev, Boyko Ch Atanasov, Tsanko I Yotsov, Dimitar Bozhidarov Hadzhiev, Simon E Stock, Chukwuemeka Gerald Nwegbu, Tanyi John Tanyi, James A Brown, Jugpal S Arneja, Susan M Lee, Ramya Kancherla, Biniam Kidane, Pierre-Olivier Champagne, Xiya Ma, Allana Munro, Dolores M McKeen, Janet Martin, Juan Glinka, Edward M Vasarhelyi, Yamini Subramani, Hilda Alfaro, Ushma J Shah, Nelson J Gonzalez, S Danielle MacNeil, Mahesh Nagappa, Richard A Malthaner, Muriel Brackstone, Nawar A Alkhamesi, Mehdi Qiabi, Camila Arango-Ferreira, Agya B A Prempeh, Sinziana Dumitra, Richard T Spence, Eric LR Bedard, Susan M Lee, Jessica GY Luc, Brian R Johnston, Najmedden Attabib, Amit RL Persad, Sunit Das, Amir Khoshbin, Karim S Ladha, Ashwin Sankar, Bijan Teja, Julian F Daza, Veronica F Chan, Reto M Baertschiger, Augusto Zani, Carolyn Nessim, Daniel I McIsaac, Mandeep Singh, Abdollah Behzadi, Angela J Dell, Salim M Al Riyami, Khaled Z Dajani, David Bigam, Vinod K Manikala, John T Street, Kelly V Mayson, Christopher J D Wallis, Ximena Mimica, Maria Marta Modolo, Julio Villanueva, Roberto Altamirano, Sofia Waissbluth, Diego I Marín, Maricarmen Olivos, Bruno Catoia Fonseca, Andrés J Hodali, Andrea I Ramos, Marco A Valenzuela, Janina J Torres, Yi Song, Wah Yang, Mohammed Safi, Abdullah Aldanakh, Mohammed Alradhi, Yidong Lyu, Yan Chen, Angélica V Fletcher, Daniela Camargo, Rafael Figueroa Casanova, Camilo Andres Caicedo Medina, Dinimo Bolivar, Tatiana Carolina Beltran Garcia, Nestor F Pedraza, Andrea Garcia-Lopez, Nasly G Patino-Jaramillo, Fernando A Giron, Carlos J- Perez Rivera, Albaro José Nieto-Calvache, Fredy Ariza, Claudia Milena Orozco-Chamorro, Maria A Nanez, Diana S Garces, Luis M Figueroa, Marisol Badiel, Delio F Martinez, Brenda Coll-Tello, Hector F Camelo, Antonio J Montoya Casella, Sebastian Ordoñez, Paola A Velez Sanchez, Juan C Salcedo, Lina M Villegas, Jorge A Holguín, Jesús Hernán Tovar Cardozo, Jorman Harvey Tejada Perdomo, Valentina Gutiérrez Perdomo, Natalia A Rivera-Rincon, Paula Torres Gomez, Elena Leonor Delgado-Nieto, Andres Isaza-Restrepo, Felipe Vargas, Ana M Vargas, Arnulfo Andrade Castro, Jorge A Navarro, Saul E Vargas, Jose A Calvache, Maria C Mendoza-Arango, Jorge Luis Vélez Bernal, Felipe O Gonzalez, Goran šantak, Iva Kirac, Dorian Kršul, Ana Bosak Versic, Goran Augustin, Tomislav Kulis, Zeljko Kastelan, Ana Danic Hadzibegovic, Kresimir Grsic, Tvrtko Hudolin, Marko Tarle, Matija Mamic, Mia Lorencin, Ivica Luksic, Dubravko Habek, Suzana Konjevoda, Jakov Mihanovic, Stavros A Antoniou, Heyam A Almezghwi, Nikolaos Gouvas, Lubomir Martinek, Rene Novysedlak, Jan Žatecký, Peter Christensen, Christian S Meyhoff, Mark Bremholm Ellebæk, Sylvia Jeanne Batista, Julia Rodriguez, Dolores Mejia De la Cruz, Mirna Giselle Santiago Jimenez, Carla M Dominguez, José R Negrete, Pedro N Campuzano, Daniel L Mogrovejo, Maria J Armas, Jenny E Arboleda-Bustan, Eddy P Lincango-Naranjo, Mohamed El-Kassas, Ahmed K Awad, Emad Alazab, Kyrillos G Abdulmaseh, Sherein Diab, Mostafa HAbd El Wahab, Amr Darwesh, Badr E Mostafa, Mahmoud Shaban Abdelgalil, Merihan A Elbadawy, Ali M Reda, Amir Fathi Asla, Notaila M Fayed, Mohamed S Ahmed, Menan Ahmed Elsadek, Dalia Elsayed Gad, Aya Gameel El Saadany, Aalaa Mohamed Elsadek, Amir Fathi Asla, Ahmed E Sayed, Ahmed Naeem, Abdullah Al-Mallah, Ahmed A Abdelsamed, Moataz Ewedah, Mohamed O Soliman, Yousef Tanas, Mohammed Hamouda, Marina H Mahfouz, Manal E Abdo, Yomna E Dean, Karim Lka, Aya O Abodeeb, Fouad M F B Ashoush, Roqaia R Elsherbiny, Mohamed Gadelkarim, Nermin A Osman, Maya MIbrahim, Nehal G Youssef, Mohamed Hamdy Ibrahim, Antonios Soliman, Rabea A Gadelkareem, Ahmed M Abbas, Aliae AR Mohamed Hussein, Khaled Abdelsattar, Ahmed Maher, Mohamed M Elabd, Hassan Abdelazim, Maher H Ibraheem, Yasser A Noureldin, Mahmoud Elfiky, Mohamed A Ebrahim, Ahmed Saber Mohamed Abdelrahman, Mahmoud Marei Marei, Aya M Elkhalawy, Ahmed Y Azzam, Mohammed A Azab, Ahmed H Elmasry, Ahmed K Awad, Amr Elgazar, Mahmoud Mohamed Mohamed Shalaby, Mohammad S Mahmoud, Mohamed G Qassem, Hussein Kinani, Abdelrahman M Wahba, Merihan A Elbadawy, Rana Hisham Ezzat, Mai H Ahmed, Mohamed Elemam Elshawy, Hazem Metwally Faragalla, Khalid D Mahmoud, Ahmed M Nafea, Mohamed Abdel-Maboud, Hesham Abozied, Modather Moharam, Ashraf H Shehata, Samir A ElKafrawy, Mosaab M Tayiawi, Hosam M Elghadban, Moataz M Emara, Ahmed Shehta, Amira M Saqr, Wafaa M Abdelelsalm, Eslam M Elshennawy, Samar T Radwan, Selmy S Awad, Sameh H Emile, Wesam A Aldosoky, Hossam Elfeki, Sara N Gendi, Hala Adel Abdelsalam, Mohammed Hammad, Mostafa Shalaby, Ahmad Hammad Sakr, Mohamed A Abdelmaksoud, Mohammed Alawady, Abdelrahman Azzam Omran, Abdallah R Allam, Zainab Ismail, Khaled M Gaballah, Mahmoud Fathy Mahmoud AlGady, Ahmed M Raslan, Khaled Gharbia, Abdelazez A Nuser, Ahmed Kamal Sayed, Abdullah Al-Mallah, Mahmoud A Elshahawy, Galal Ghaly, Ahmed Elshawadfy Sherif, Abdelrahman M Makram, Omar M Makram, Ola Ahmed, AbdelRahman M A Helmy, Khaled M Abdelwahab, Mohamed Abdelkhalek, Islam H Metwally, Mosab Saad Shetiwy, Mohammad Zuhdy, Salma I Ramadan, Mohamed Abdelghany, Mohammed A Omar, Ziad A Soliman, Hossam T Ali, Salma Elnoamany, Sherief Ghozy, Alzhraa S Abbas, Mostafa A Shehata, Sahar A Mahmoud, Mohammed A Elsaman, Elsayed A Fayad, Asmaa Radwan, Ahmed I El-Sakka, Asser Sallam, Mohamed G Elbahnasawy, Eslam S Esmail, Ahmed Maher Hawila, Mohamed K Hamada, Sara H Motawea, Mohamed S Morsy, Hatem Refaat El-Sheemy, Mahmoud Ahmed Ebada, Ali H Khedr, Ahmed Gad, Omar Elmandouh, Reem Elmandouh, Souad Alkanj, Mohammad G Youssef, Kamal Awad, Maged Mohammed, Ahmed H Elsayad, Tõnu Rätsep, Melatework A Wolle, Abraham G Negussie, Misganaw A Adimass, Bereket Tsegaye Misganaw, Yoseph S Bezabih, Biniam Zemedu Assefa, Getachew W Shumye, Mengistu G Mengesha, Dagnachew Y Gechera, Adnan A Mohammed, Gersam A Mulugeta, Yonas Y Metaferia, Ashebir B Kifetew, Eyueal A Degefa, Yadani M Deressa, Kebebe Bekele Gonfa, Zewdie G Bedane, Alem M Ayalew, Henok Teshome Ayele, Engida Abebe, Bereket Atnafu Worku, Million M Sisay, Dawit Worku Kassa, Atalel F Awedew, Abera C Bayable, Abraham Genetu Tiruneh, Samuel Hailu, Yilkal T Numaro, Yonas Ademe, Abat S Baleh, Thomas B Megerssa, Segni Kejela, Habtamu T Derilo, Yemisirach B Akililu, Iris Lebbe, Elise K Sarjanoja, Joonas H Kauppila, Juha-Jaakko Sinikumpu, Salvatore Giordano, Elie Kantor, Romy Soussan, Cipolat Mis Tommaso, Francesco Nappi, Tristan Morichau-Beauchant, Julien Nahum, Jean-Michel Maillet, Mathieu Godement, Lionel Jouffret, Federico Migliorelli, Belinda De Simone, Laurent Brunaud, Thomas Fuchs-Buder, Sylvie Testelin, Kim Bin, Sophie Boucher, Françoise Schmitt, Zaher Lakkis, Luke Harper, K Slim, Guilaume Piessen, Clarisse Eveno, Quentin Ballouhey, Abdelkader Taibi, Vincent Crenn, Emilie Duchalais, Alexis P Arnaud, Olivier Azzis, Jean-Jacques Tuech, Charlotte Vaysse, Ariane Weyl, Kelig Vergriete, Helene Charbonneau, Anne-Cecile Ezanno, Brice Malgras, Celeste Del Basso, Igor Duquesne, Federico Bernabei, Pierre-Raphaël Rothschild, Olivier Abbo, Gilles Manceau, Alexandre Chamouni, Célia Crétolle, Laurent Arnalsteen, Elie Mikhael, Andrea Police, Rosa Montero-Macias, Vincent Villefranque, Emeline Maisonneuve, Tristan Langlais, Barbara Seeliger, Patrick Pessaux, Cristians A Gonzalez, Antonio D'Urso, Martina A Angeles, Agathe Seguin-Givelet, Marc Danguy Des Deserts, Sebastien Gaujoux, Charles de Ponthaud, Emmanuel J Chartier-Kastler, Liza Ali, Matthieu Peycelon, Diane Mege, Zaza Demetrashvili, Mircea G Stoleriu, Lena Keppler, Tim Saier, Christian Konrads, Christian Tapking, Carsten Kamphues, Dirk R Bulian, Andrea Schmedding, Johannes Doerner, Anna E Gut, Jens Rolinger, Andreas Kirschniak, Lars Schröder, Daniel Reim, Seyer Safi, Andreas M Fichter, Arthur Wagner, Bernhard Meyer, Jens Gempt, Armin R Sablotzki, Jonas Herzberg, Manuel Altenburg, Ferhat Yenilmez, Jan Meins, Louai A Aghwan, Nikolaus Börner, Alexander M Keppler, Markus Albertsmeier, Steffen Seyfried, Marie-Claire Rassweiler-Seyfried, Maximilian Kriegmair, Karl-Friedrich Kowalewski, Konstantinos Gousias, Johanna J Strotmann, Philipp Höhn, Julian Horn, Julia M Knipschild, Leonie Siemen, Andreas Minh Luu, Raymund E Horch, Aaron Lawson McLean, Judith Anne Teresa Lindert, Sebastian Ziemann, Ali Modabber, Philipp Winnand, Frank Hölzle, Björn Sommer, Sebastian Wolf, Ehab Shiban, Florian Recker, Erdem Güresir, Thomas M Randau, Agi Güresir, Markus Velten, Tim O Vilz, Maria Wittmann, Maria A Willis, Tim R Glowka, Ulrich Bork, Matthias Hecker, Andreas Hecker, Martin Reichert, Clemens Miller, Marcus Nemeth, Ulrich Ronellenfitsch, Jorg Kleeff, Kerstin Lorenz, Ulrich Kisser, Rick Schneider, Ingmar Seiwerth, Georg Osterhoff, Valerie C Linz, Michael R Mallmann, Alexander C Rokohl, Ludwig M Heindl, Philomena A Wawer Matos, Claus Cursiefen, Christoph A Mallmann, Christian M Domroese, Alfred Königsrainer, Can Yurttas, Karolin Thiel, Julius M Vahl, Armin Wiegering, Johan F Lock, Annika Heuer, Alonja Reiter, Martin Stangenberg, Arne Böttcher, Daniel Kaemmerer, Kofi T Mensah, Frank E Gyamfi, Isabella N M Opandoh, Emmanauel O Ofori, Ebikela I Baidoo, Richard O Baidoo, Diallo A Azize, Peter Appiah-Thompson, Evans K Agbeno, Sebastian Ken-Amoah, Ganiyu A Rahman, Richard Kpangkpari, Luke A Aniakwo, Michael Nortey, Meshach M Agyapong, Benedict Boakye, Philip Mensah, Kwasi Agyen-Mensah, Mabel P Amoako-Boateng, Samuel Mensah, Sam Debrah, Mustapha Yakubu, Leslie Issa Adam-Zakariah, Anthony Davor, Joshua Arthur, Mawutor Dzogbefia, Anna Konney, Thomas O Konney, Michael Amoah, Isaac Barnor, Mohammed Duah Issahalq, Paa Ekow Hoyte- Williams, Wilfred Sam Awortwi, Bernard Hammond, Ronald Awoonor-Williams, Nuhu N H Naabo, Adu Appiah-Kubi, Kekeli Kodjo Adanu, Joe Nat A Clegg-Lamptey, Jefferson Owusu Adae, Theophilus T K Adjeso, Mundashiru Yahaya, David A Ansah-Agyei, Ana Maria Simono Charadan, Magdiel Rodriguez Labrada, Adamu Issaka, Iddrisu B Yabasin, David A Antwi, Lukman Manan, Mohammed I S Bukari, Alexis D B Buunaaim, John Abanga Alatiiga, Mohammed Sheriff, Emmanuel O Kumi, Gilbert B Bonsaana, Georgia Micha, Nikolaos Kiriakopoulos, Konstantinos Stroumpoulis, Konstantina Kalopita, Ioannis Grypiotis, Kyriakos A Psarianos, Theodoros Aslanidis, Dimitris P Korkolis, Evangelos Fradelos, Alexandra Arvanitaki, Anastasia Prodromidou, Nikolaos Thomakos, Charalampos Theofanakis, Kyveli Angelou, Dimitrios Haidopoulos, Michail Diakosavvas, Leonidas Chardalias, Ioannis Papaconstantinou, Pantelis T Antonakis, Dimitrios Politis, Dionysios Dellaportas, Christina I Kontopoulou, Nikolaos A Memos, Antonios Gklavas, Konstantinos Bramis, Panagiotis Pappas, Thalia Petropoulou, Argyrios Ioannidis, Dimitrios Ntourakis, Dimitrios Papageorgiou, Dimitrios K Manatakis, Christos G Barkolias, Dimitrios Balalis, Nikolaos P Tasis, Theodoros A Sidiropoulos, Nikolaos V Michalopoulos, Maria Papadoliopoulou, Stavros Parasyris, Nikolaos Danias, Panteleimon Vassiliu, Zoe Petropoulou, Ioannis Margaris, Eirini Kefalidid, Dimitrios Papaconstantinou, Kosmas I Paraskevas, Alexandrina S Nikova, Theodosis Kalamatianos, Konstantinos Stamatis, Maria Sotiropoulou, George Stylianidis, Gregory P Kouraklis, Anna Paspala, Constantinos Nastos, Dimitrios Sfoungaris, Ioannis A Valioulis, Dimitrios Raptis, Nikolaos Tsakiridis, Konstantinos Alexandros Tsakiridis, Konstantinos Arvanitakis, Christos Kalfountzos, Georgios D Koukoulis, Konstantinos Bouliaris, Vasileios A Lachanas, Christos A Doudakmanis, Christos Chouliaras, Aristeidis Papadopoulos, Maria P Ntalouka, Dimitrios Magouliotis, Maria Fergadi, Athina A Samara, Grigorios Christodoulidis, Metaxia Bareka, Thanos Athanasiou, Eleni M Arnaoutoglou, Jiannis Hajiioannou, Konstantinos Perivoliotis, Ioannis Baloyiannis, Fragkiskos A Angelis, Konstantinos G Stamoulis, Dimitrios Symeonidis, Christos Korais, Eleni Gkrinia, Anna-Maria Ntziovara, Francesk Mulita, Konstantinos Bouchagier, Georgios I Verras, Maria I Argentou, Michail Vailas, Stylianos Germanos, Panagiotis Tavlas, Dimitris Tatsis, Ioannis T Astreidis, Alexandros Louizakis, Asterios Antoniou, Konstantinos Paraskevopoulos, Georgios Chrysovitsiotis, Maximos Frountzas, Konstantinos G Toutouzas, Aristeidis Chrysovergis, Spyridon Potamianos, Efthymios Kyrodimos, Vasileios Papanikolaou, George Theodoropoulos, Tania Triantafyllou, Andreas Larentzakis, Athina-Despoina Kimpizi, Ioannis Tsakiridis, Georgios Kapetanios, Themistoklis Dagklis, Stamatios Petousis, Chrysoula Margioula-Siarkou, Efstratia Baili, Ekaterini C Tampaki, Eftychios Lostoridis, Emmanouil C Avramidis, Andreas P Efstathiou, George C Babis, Konstantinos Roditis, Paraskevi V Tsiantoula, Nikolaos Machairas, Dimitrios Schizas, Stylianos Kykalos, Panagiotis I Dorovinis, Paraskevas Stamopoulos, Alexandros K Charalabopoulos, Theodore Liakakos, Elias Koziakas, Ioannis Karavokyros, Antonia Skotsimara, Athanasios Syllaios, Gerasimos S Tsourouflis, Nefeli K Tomara, Angelos Dimas, Konstantinos G Apostolou, Ioannis Tsouknidas, Evangelia Samara, Nikolaos A Papakonstantinou, Areti Falara, Kyriakos Papavasiliou, Ioannis D Siasios, Christos Kaselas, Christos Anthoulakis, Konstantinos Tigkiropoulos, Eleftherios Spartalis, Panagiotis Mourmouris, Konstantinos Tsekouras, Lazaros Tzelves, Georgia Dedemadi, Stylianos Gaitanakis, Athanasios Marinis, Konstantinos Stamatiou, Pinelopi D Vlotinou, Sofia Xenaki, Konstantinos Lasithiotakis, Taxiarchis Konstantinos Nikolouzakis, Agathi Karakosta, Petros Tzimas, Panagiotis Charatsaris, Gustavo Recinos, Marlon D Vega, Maria L Aguilera, Pablo J Rivera, Dianne A Sosa, Tania A Salazar, Natalia I Ybarra, Ever E Morataya, Estuardo J Brolo, Andrea M Lowey, Jose R Paiz, George KC Wong, Samuel KK Ling, Calvin SH Ng, Rainbow WH Lau, Kaori Futaba, Dezso Toth, Attila Zaránd, Laszlo Piros, John A Santoshi, Manoj Nagar, Adesh Shrivastava, Zainab Ahmad, Prateek Behera, Megha Gautam, Dinesh Bagaria, Apoorva P Kabra, Samarth Mittal, Piyush Ranjan, Shilpa Sharma, Vivek Trikha, Dinesh Kumar Bagaria, Junaid Alam, Prabudh Goel, Surya Kumar Dube, Narendra Choudhary, Ramesh P Menon, Rajkumar Kottayasamy Seenivasagam, Abhishek Agrawal, Kinjal S Majumdar, Pranati Sharma, Amit Gupta, Rajnish K Arora, Poonam Arora, Somprakas Basu, Farhanul Huda, Lena E David, Aakansha G Goswami, Rajat Piplani, Mahesh Sultania, Sujit K Tripathy, Tushar S Mishra, Dillip Kumar Muduly, Saubhagya Kumar Jena, Abhijeet Mishra, Jayanta K Mitra, Sweta Singh, Ranjit Kumar Sahu, Chitta R Mohanty, Saubhagya K Jena, Ritesh Panda, Kiran Kumar Boyina, Saubhik Dasukil, Nitesh Gahlot, Naren P Khatri, Amanjot Kaur, Jeewan R Vishnoi, Naveen Sharma, Ankita Chugh, Mahendra singh, Sourabh S Chakraborty, Anupama Rajanbabu, Reem Hunain, Monish S Raut, Diwakar Pandey, Raghubir Srivastava, Ajesh Raj Saksena, Mebanshanbor Garod, Bhargavi R Budihal, Shankarsai Kashyap, Pavani B Agarwal, Swati Chhatrapati, Charulata Deshpande, Lipika Amresh Baliarsing, Kalpana balakrishnan, Ahmed Sayeed Tanweer, Parvez David Haque, Sathiafrey D A Chitresh, Swati Daniel, Rohini Dutta, Uma Kant Dutt, Karan Garg, Mukul Garg, Christina George, Dhruva Ghosh, Pariza Gupta, Ritu Jain, Jeffrey A Kalyanapu, Savleen Kaur, Ankita Khurana, Sarita Khurana, Jatin Kumar, Dootika Liddle, Amit Vipan Mahajan, Pranay Pawar, Konda Samuel Paul Pradeep, Reuben R Ranadive, Arti Rajkumar, Vivin Daniel Sam, Jerrin Regi Sam, Habie Thomas Samuel, Sangeetha Samuel, Prateek Sahi, Aditya Sood, Nitish Srivastava, Alen J Thomas, Naveen J Thomas, Jacob K Varkey, Vigy Georgekutty Vazhakalayil, Rahul William, Rohin Mittal, Sreekar Devarakonda, Jeyashanth Riju, Vinotha Thomas, Moonish V Sivakumar, Rajeevan Philip Sridhar, Gilbert S Jebakumar, Negine Paul, Albert A Kota, Pushplata Kumari, Suraj Surendran, Raji Suraj, Naveen Sundaram Victor, D R Kathir Joyson, Vidya Konduru, Kashish Malhotra, Ashwin Rammohan, Mohamed Rela, Vaibhav Jain, Ashish Jakhetiya, Vidhi K Patel, Karuna Sree Pendyala, Manisha Aggarwal, Shyam K Gupta, Ashwani Kumar, Manpreet Singh Bindra, I Yadev, Meer M Chisthi, S Soumya, Sachit Anand, Jyotsna Rani, Kanika Sharma, Indranil Ghosh, Shalini Sundaraju, Prasanth Penumadu, Krishna Kumar Govindarajan, Ramanitharan Manikandan, Alfie J Kavalakat, Ashish Phadnis, Piyush Jadhao, Shankar Subbarayan, Reem Hunain, Gabriel Rodrigues, Sufyan Ibrahim, Zeeshan BM Hameed, Sanoop K Zachariah, Irappa V Madabhavi, Varun V Bansal, Shiv Rajan, Ahmad Ozair, Akhilanand Chaurasia, Pooja Ramakant, Manju L Verma, Ayushi Shukla, Anjoo Agarwal, Ankur Bajaj, Somil Jaiswal, Brijesh Mishra, Yuvaraja Thyavihally, Santosh S Waigankar, Santosh Subhash Waigankar, Siddhi Hegde, Philip V Alexander, Rahul Deo Sharma, Vivek M Sodhai, Kunal Kishore, Ramya M Vishweshwara, Lovenish Bains, Sanjeev Kumar, Akshat Malik, Zahiya Hareem Shaikh, Priyanka Kumari, Jerin J Thomas, Sanjay Kumar Yadav, Ritika Dhurwe, Upamanyu Nath, Hitesh Chopra, Vishal Kumar, Lileswar Kaman, Madhivanan Karthigeyan, Manjul Tripathi, Sandeep Mohindra, Pravin Salunke, Kavindra Singh, Karthick Rangasamy, Nirmal Raj Gopinathan, Anshul Siroliya, Vidyadhar B Bangal, Ashish Gupta, Lavanya Kannaiyan, Aditya A Kulkarni, Bijnya B Panda, Abhishek Mittal, Rahul J Ghodke, Sachin Y Kale, Sanjay Dhar, Gaurav Agarwal, Anjali Mishra, Vijai Datta Upadhyaya, Basant Kumar, Madhan Jeyaraman, Asif Mehraj, Fazlul Q Parray, Shivang Gaurang Amin, Saptak P Mankad, Karan V Thakore, Riya Singh, Pankaj Kumar Garg, Hardil P Majmudar, Tanishq S Sharma, Raghunandan Gorantlu Chowdappa, Sahiba S Maniar, Sumit Thakar, Kavitha Jain, Tapan Patel, Rahul A Gupta, Gaurav Aggarwal, Sujoy Gupta, Sanjit Kumar Agrawal, Abhishek Sharma, Prateek Jain, Anik Ghosh, Amrit Pipara, C S Pramesh, Shraddha Patkar, Vijaya Prakash Patil, Jigeeshu V Divatia, Ajay Puri, Akshay Kumar, Rohit Bhardwaj, Abhishek Mittal, Sunil Kumar Venkatappa, Mallikarjuna Manangi, Prashanth J Prabhu, Sumadi L Anwar, Djayanti Sari, Aida R Tantri, Susilo Chandra, Sidharta K Manggala, Aino N Auerkari, Raihanita Zahra, Ratna F Soenarto, Andi A W Ramlan, Matthew Billy, Achmad K Harzif, Ilham Utama Surya, Mayang I Lestari, Fachreza A Damara, Rozi A Aryananda, Yunus Kuntawi Aji, Thirza Hadipranata, Warren Lie, Gabriele J Kembuan, Marilaeta Cindryani, Tjokorda Gde Agung Senapathi, Christopher Ryalino, Elahe Hosseini, Alireza Hosseini, Pourya Medhati, Reza Erfanian, Mohammadreza Firouzifar, Mahtab Rabbani Anari, Shirin Irani, Fakher Rahim, Naser Yousefzadeh Kandevani, Fatemeh Sheikholeslami Kabiri, Nima Najafian Motahaver, Masoomeh Hosseinpoor, Mohsen Rajati, Reza Assadi, Mohadeseh Haqgou, Seyed Amir Javadi, Faramarz Karimian, Mehdi Asadi, Narges Alizadeh, Mohammad Heidari, Seyed Fakhreddin Hejazi, Narges Alizadeh, Vahid Bazyari, Sayedali Ahmadi, Hossein Yusefi, Mojtaba KA Attar, Leila Oryadi Zanjani, Mohammad Hossein Nabian, Seyed Reza Yahyazadeh, Hassan Fatemi Manesh, Mohadese Sotudeh, Hamed Akhavizadegan, Seyyed Hossein Shafiei, Hogir I Aldawoody, Ahmed A Almusawi, Ali Al-Isawi, Ahmed Basim Abed Al-Hajjaj, Yasir A Zwain, Mohammed J Alwash, Najah R Hadi, Rasool Maala, Aeshah Anwar Adil, Hashim Talib Hashim, Naseem W Al-Salihi, Fahad Majid Yaseen Al-hasani, Pakhshan A Rashed, Pakhshan A Muhamed, Ahmed A Hilmi, Mohammed Musa A Akhtyare, Hashim T Hashim, Rand A Hussein, Lylas Aljohmani, Fiona E Crotty, Jessie A Elliott, Mohsen Javadpour, Niall F Davis, James PC Ryan, Muyiwa Aremu, Stephen J O'Brien, Benjamin Ngie Xiong Wong, Michelle Min Hsiao, Emmet Andrews, Jacques Pretorius, Imran Azeem, Hilary Ikele, Claire M McCarthy, Fadi-Tamas Salameh, Donal B O'Connor, Clare O'Connor, Patrick Sheahan, Conor P Barry, Fergal G Kavanagh, Deirdre Callanan, Danielle L James, Cillian Clancy, Stefanie M Croghan, Thomas M Aherne, Aoife Kiernan, Patrick W Owens, Ben Creavin, Hassan Mekki, Stewart R Walsh, Paul A Carroll, Ke En Oh, Aoife J Lowery, Miklosh Bala, Noam Shussman, Jonathan Abraham Demma, Gad Marom, Yuri Fishman, Osnat Zmora, Limor Muallem Kalmovich, Nir Horesh, Roi Anteby, Mario V Papa, Giulio Argenio, Giulio Sozzi, Chiara Amatucci, Edoardo Segalini, Giovanni Pesenti, Alessandro Giani, Michele Mazzola, Pietro Maria Lombardi, Alberto M Saibene, Nicoló M Mariani, Luca Zanin, Jacopo Andreuccetti, Federico Ferrari, Gian Luca Baiocchi, Alice Frontali, Stefano Granieri, Christian Cotsoglou, Marco Scarpa, Roberto Colasanti, Donatella Schiavone, Antonio Castaldi, Carmine Antropoli, Gabriele Colò, Irene Fiume, Gaetano Poillucci, Laura Fortuna, Luca G Locatello, Oreste Gallo, Giandomenico Maggiore, Andrea Bottari, Chiara Bruno, Giuseppe Barbato, Annamaria Di Bella, Antonio Taddei, Matteo De Pastena, Tommaso Campagnaro, Giuseppe Malleo, Salvatore Paiella, Alberto Balduzzi, Vito Andrea Capozzi, Alessandro Carretta, Giacomo Bertolini, Giorgio Dalmonte, Mario Giuffrida, Valeria Andriola, Gennaro Martines, Arcangelo Picciariello, Gianmaria Casoni Pattacini, Mattia Di Bartolomeo, Alexandre Anesi, Herald Nikaj, Sergio Gentilli, Elisa Reitano, Giacomo Fiacchini, Gregorio Di Franco, Luca Morelli, Lorenzo Andreani, Dario Tartaglia, Riccardo Balestri, Federico Coccolini, Massimo Chiarugi, Marco Puccini, Daniele Fusario, Osvaldo Carpineto Samorani, Luigi Marano, Ludovico Carbone, Franco Roviello, Valeria Restaino, Anna Lisa Pesce, Luca Resca, Stefania Angela Piccioni, Massimiliano Veroux, Giuseppe Sarpietro, Maria Grazia Matarazzo, Antonio Cianci, Andrea Morini, Maurizio Zizzo, Valentina Mastrofilippo, Vincenzo Dario Mandato, Lorenzo Aguzzoli, Jlenia Sarnari, Gabriela E Nita, Nicolò Fabbri, Michele Rubbini, Roberta Tutino, Mauro Podda, Gian Luigi Canu, Enrico Peiretti, Sokol Trungu, Mario D'Oria, Andrea Lauretta, Matteo Marro, Francesco Guerrera, Mauro Santarelli, Stefano Salizzoni, Oreste Iocca, Pasquale Di Maio, Teresa Perra, Alberto Porcu, Antonio M Scanu, Giovanni Pirozzolo, Francesca Toia, Ettore Dinoto, Emanuele Cammarata, Mara Franza, Fernando Rosatti, Calogero Cipolla, Natalia Di Grazia, Walter R Milia, Felice Pecoraro, Edoardo Virgilio, Andrea Barberis, Fabrizio Bàmbina, Laura Lavalle, Giovanni Sinibaldi, Leo Licari, Francesca P Tropeano, Gaetano Luglio, Gianluca Pagano, Francesca Paola Tropeano, Roberto Peltrini, Maria Michela Di Nuzzo, Umberto Bracale, Alice Indini, Daniele Bissacco, Maurizio Domanin, Sara Torretta, Giorgio Bogani, Fabio Martinelli, Laura Sala, Umberto Cortinovis, Valeria Zingarello, Francesca Bertolina, Moh'd Abu Hilal, Pietro Fransvea, Angelo A Marra, Fausto Rosa, Francesco Litta, Carlo Ratto, Angelo Parello, Silvia Tedesco, Federica Ferracci, Sara Pitoni, Sabatino D'Archi, Gianluca Franceschini, Lorenzo Scardina, Gianpiero Gravante, Luigi Conti, Edoardo Baldini, Pietro Maniscalco, Corrado Ciatti, Giuseppe Spriano, Giuseppe Mercante, Francesca Gaino, Flavio Milana, Antonino Spinelli, Fabio Ferreli, Armando De Virgilio, Matteo Di Bari, Fabrizio Aquilino, Fabio Marino, Raul Pellini, Flaminia Campo, Silvia Moretto, Francesco Mazzola, Gerardo Petruzzi, Riccardo Mastroianni, Giuseppe Simone, Matteo Rottoli, Iris S Russo, Diego Raimondo, Ignacio J Fernandez, Antonio Raffone, Pietro Bertoglio, Matteo Ravaioli, Giuliana Germinario, Paolo Bernante, Paolo Casadio, Renato Seracchioli, Matteo Droghetti, Riccardo Schiavina, Francesco Ricotta, Achille Tarsitano, Alessandro Arena, Anna Nunzia Della Gatta, Tommaso Violante, Alice Pellegrini, Federico Bolognesi, Piergiorgio Solli, Sara Ricciardi, Alessandro Cipolli, Manuela Maletta, Marilina La Porta, Maria Paola Lauretta, Rita M Melotti, Niccolò Daddi, Sergio Nicola Forti Parri, Elena Garelli, Anna M Perrone, Raffaele Lombardi, Valentina Pinto, Marco Pignatti, Valeria Tonini, Chiara Copelli, Antonio Nicola Giordano, Vincenzo Palai, Raffaele Aspide, Emanuele La Corte, Stefano Lucchini, Francesco Castagnini, Francesco Pardo, Michele Di Liddo, Filippo Caternicchia, Danilo Donati, Bruno Cavalieri, Tommaso Frisoni, Marco Rotini, Stefano Scabini, Aldo Vagge, Lorenzo Ferro Desideri, Fabio Barra, Marco Sparavigna, Piero Fregatti, Andrea-Pierre Luzzi, Sergio Costantini, Simone Ferrero, Claudio Gustavino, Marco Paratore, Umberto Perrone, Maria Grazia Centurioni, Franco Alessandri, Antonella Ferraiolo, Francesco Paolo Rosato, Lorenzo Ball, Francesca Ascari, Giuliano Barugola, Andrea Lovece, Pamela Milito, Stefano Siboni, Luigi Bonavina, Alberto Aiolfi, Davide Bona, Giancarlo Micheletto, Luca Bertolaccini, Giulia Sedda, Lorenzo Spaggiari, Marta Tagliabue, Rita De Berardinis, Giacomo Pietrobon, Francesco Chu, Mohssen reAnsarin, Annalisa Garbi, Renato Patrone, Andrea Belli, Pasquale Cianci, Ivano Raimondo, Annamaria Ferrero, Carlo Alberto Pacilio, Antonio Bocchino, Leonardo Solaini, Fabrizio D'Acapito, Barbara Di Stefano, Ruggero M Corso, Francesco Pata, Mariarosaria Vitale, Giuseppe Rotunno, Riccardo Lenzi, Ernesto Migliorino, Ugo Grossi, Simone Novello, Maurizio Romano, Serena Rossi, Giacomo Zanus, Angelo G Epifani, Alessandro Broglia, Matteo Santoliquido, Marco Clementi, Chiara Marafante, Francesco Maria Carrano, Renato Patrone, Francesco Fleres, Guglielmo Clarizia, Guido Coretti, Luca Ferrario, Claudio Guerci, Anna Maffioli, Marcello D'Andrea, Nicola Zanini, Riccardo Bertelli, Carlo Vallicelli, Fausto Catena, Gian Marco Prucher, Alfredo Conti, Gianluigi Moretto, Marco Inama, Manuela Grivon, Daniele Sambucci, Giacomo M Pirola, Marilena Gubbiotti, Andrea Sagnotta, Sara Ornaghi, Robert Fruscio, Nicolò Tamini, Marco Ceresoli, Luca Gianotti, Fabrizio Masciello, Tommaso Nelli, Giuseppe Canonico, Alessandro Anastasi, Michele Malerba, Emmanuele Abate, Vincenzo Lizzi, Antonio L Sarni, Nicola Tartaglia, Marco Montagna, Stefano D'Ugo, Norma Depalma, Marcello Spampinato, Paolo Pizzini, Stefano Magnone, Marcello Migliore, Alessio Volpicelli, Rossella Gioco, Giorgio Ivan Russo, Antonio Bozzani, Lorenzo Cobianchi, Francesca Calabretto, Enrico Pinotti, Mirko Barone, Michela Campanelli, Giulia Bagaglini, Leandro Siragusa, Luca Orecchia, Marzia Franceschilli, Roberta Angelico, Bruno Sensi, Tommaso M Manzia, Lorenzo Petagna, Giulia Bacchiocchi, Giuseppe S Sica, Pierfrancesco Lapolla, Andrea Picchetto, Placido Bruzzaniti, Giovanni Marruzzo, Antonio V Sterpetti, Andrea Mingoli, Paolo Sapienza, Anthony Kevin Scafa, Giuseppa Zancana, Gioia Brachini, Diego Ribuffo, Bruno Cirillo, Simona Meneghini, Pierfranco M Cicerchia, Martina Zambon, Vito D'Andrea, Alessia D'Amico, Pietro Familiari, Andrea Cassoni, Resi Pucci, Francesca De Felice, Giuseppe Pascarella, Alessandro Strumia, Alessandro Coppola, Biagio Zampogna, Rocco Papalia, Gabriella T Capolupo, Marco Caricato, Antonio Nenna, Carmelo Dominici, Maria Caffo, Giorgio Badessi, Carmelo Mazzeo, Gerardo Caruso, Gabriele Bellio, Eleonora Guaitoli, Roberto Rimonda, Federico Fusini, Marco Giacometti, Caterina Baldi, Francesco Ferrara, Antonella Chessa, Giulio Accarino, Michela Monteleone, Carlo Riva, Arianna Balconi, Marko Markovic, Gisella Barone, Andrea Locatelli, Simone Olmetti, Andrea Costanzi, Matteo Uccelli, Raffaele Galleano, Andrea Balla, Antonio De Carlo, Andrea Pisani Ceretti, Luca Bertoglio, Alessandro Grandi, Luca Apruzzi, Andrea Melloni, Michael Spartalis, Alfio Spina, Paola De Nardi, Giulia Bonavina, Massimo Candiani, Martina Piloni, Gianluca Nocera, Filippo Gagliardi, Stefano Turi, Cosimo De Nunzio, Niccolo Petrucciani, Silvia Fiorelli, Giovanni G Laracca, Cecilia Menna, Giorgio Lisi, Alberto Brolese, Francesco A Ciarleglio, Diego Sasia, Giorgio Giraudo, Valentina Testa, Maria Carmela Giuffrida, Roberto Chiarpenello, Ettore Dalmasso, Desiree Cianflocca, Giacomo Calini, Nicola Cillara, Giulia Armatura, Luca Turati, Gianluca Pellino, Maria Paola Menna, Claudio Iovino, Settimio Rossi, Francesca Simonelli, Domenico Baccellieri, Massimo Candiani, Lorenzo Gozzini, Ugo Elmore, Riccardo Rosati, Gaetano Gallo, Giuseppe Giannaccare, Maria G Cristofaro, Ida Barca, Adriano Carnevali, Giuseppe Consorti, Antonio Simone Laganà, Alex Pontini, Renato Salvador, Francesco Di Marzo, Giulia Turri, Junichi Saito, Tsukasa Kochiyama, Sohei Satoi, Daisuke Hashimoto, Kazuhiko Yoshimatsu, Tsutomu Namikawa, Akira Kuriyama, Eiji Sunami, aChikashi Takeda, Masaki Shiota, Satoshi Toyama, Makoto Ishitobi, Yosuke Kawasaki, Masahiko Kawaguchi, Mitsuru Ida, Masae Iwasaki, Hiroshi Mase, Yuki Fujimoto, Tomohiro Chaki, Shunsuke Tachibana, Satoshi Kazuma, Naoto Kuroda, Yuka Matsuki, Kota Kamizato, Rand Y Omari, Mohammad Ahmad Jamil Es Salim, Zaid Alwarawrah, Salameh A AAbdulrahmanlarood, Adnan R Alnaser, Radi Tofaha Alhusseini, Abdulrahman G Qasem, Ahmad M Eid, Mohammad A Theab, Ibrahim Ghayada, Ali Guboug, Mohannad Fayiz Alqedrh, Mohammed E Al-banna, Amro Abuleil, Yaqin Mahmoud Asassfeh, Zaid Mohammed Al-sheikh ali, Ahmad Ayman Eid, Reem G AbuSalah, Raid George Hijazeen, Sajeda Awadi, Omar S Mansour, Almu'atasim Khamees, Bourhan Alrayes, Mohammad Hassan, Mahmoud W M Qandeel, Zainab O Ibrahim, Mohammad Maher Salah Salah, Hazem Zuhair Alnatour, Ma'moun Helmi Suleiman Saleh, Haya H Suradi, Hashem A Abu Serhan, Faris Jamal Abu Za'nouneh, Hazim R Alheji, Khayry Al-Shami, Ala'a Al-deen T Mousa, Isam K Bsisu, Rasha Bsisu, Mohammad I A Abuzenah, Zeina H Kalaji, Samir Jabaiti, Haya A Omeish, Aseel Y Almuhtaseb, Amro M Abuleil, Reem A Theab, Anagheem A Sheyyab, Shadi Hamouri, Hazim S Ababneh, Zouhair Amarin, Mohammad Yasin Bahhour, Marah K Abu-Mehsen, Mohammed Abdullah Al-howthi, Omar S S Wafi, Taher Rashed Mohammed Sawadi, Iyad S Albustami, Maen O Masadeh, Ahmad Al Khassawneh, Justin Z Amarin, Sara S Irshaidat, Mohamad K Abou Chaar, Louay Y Zaghlol, Razan Mansour, Mohammed Shahait, Haitham Qandeel, B Abd Almonem, Lubna Hawasly, Ghalia Alsabbagh, Tawfik Mohammed Al-Dabaa, Qaed Mashhour Bani Amer, Luai Abu-Ismail, Dua'a M Shaout, Tariq H Abu-shadouf, Raikhan Bolatbekova, Nadir Issayev, Mukhtar B Kulimbet, Almaz M Kiyabayev, Dinara Ospanova, Dauren Zhumatayev, Abylai Baimakhanov, Ildar Fakhradiyev, Shynar Tanabayeva, Timur Saliev, Dilyara Kaidarova, Beverly Cheserem, Intisar H S Hamdun, Aziz Z Munubi, Mark M W Siboe, Samuel Wanjara Wachera, Robert K Parker, Michael M Mwachiro, Victor Pendaeli Mwangi, Yaqoub M Jafar, Tariq F Al-Shaiji, Andrejs PÄolkins, Ingus A Apse, Hemant D Sheth, Jānis Pāvulāns, Samar Karout, Imadeddine Ahmad Farfour, Ali O Safar, Anthony Lichaa, Salim H Ismail, Mohamad B Kassab, Hussein Abou-Abbass, Rabih F Awad, Hadi El Assaad, Fatima Ghazi Serhan, Lina Karout, Anisa Chowdhary, Rania Itani, Ali A A Abu Hamrah, Almoataz Bellah, Nassib S Algatanesh, Mousab A Duwebi, Esraa T Alkouba, Hala M Algehani, Monther Alsharif, Faraj S Al-maadany, Fatimah S Elkhafeefi, Ahmad M Buimsaedah, Sarah M Ghazal, Mohamed G Amnaina, Ghozlan Y Yagoub, Hana Ramadan bin yahia, Elham Hussin Bareig, Bahaeddin BenHamida, Nayrouz Alkimeeshi, Malak Marwan, Nawal Aldokali Muhammed, Eman M Benamer, Rema H Othman, Ahmed A Momen, Kusay A Ayad, Nawal Aldokali, Alsnosy Abdullah Khalefa Mohammed, Enas F Sanousi, Saed J Aboubakr, Islam F Aboubakr, Amal Alttaira, Sara A Benatiga, Ilham A Alteerah, Wafa Aldressi, Marwa O Elhwety, Mohamed Fathi Kalifa, Maram A Glessa, Taha Abubaker, Hassan A Shembesh, Arowa Alansari, Akram M Alkaseek, Malek Mohamed Abusannuga, Mohammed A Alawami, Fras Ammar Elhajdawe, Aihab Salem Benamwor, Husayn M Aween, Eslam Kriem, Rayet Al Islam Benjouira, Sana Moussa Shagour, Hajar Alamin Ali, Ahmed I Awrayit, Salmin Ibrahim Matoug, Rema Ibrahim Abdesalam, Ikhlas M Ouakouak, Ali H Aldarraji, Ameerah Faraj Elmahdi, Zinelabedin Mohamed, Samera M Khan, Ahmed A Gerwash, Mohammed Khayri Aboubeirah, Nosaiba Jalal Drera, Marwa A Sinan, Ekram Abdulhamid Abujrad, Marwa Biala, Doaa A Gidiem, Sarah A Aljamal, Esmail M Hamuda, Hussamuddin Abusaa Manhus, Muhannud Hassan Binnawara, Muhammed Elhadi, Ahmed A Msherghi, Mohamed Ajala, Nadia D Shetty, Sanad S Kanna, Mohamed H Said, Mohamed M Elghazal, Moaz Mustafa Alwarfalli, Mohamed A Alharari, Eslam Etayeb, Anwaar M Abozid, Kariman Rdadi, Tariq Alferis, Ibrahim A Ellojli, Muad F Abuhallalah, Alhadi M Jahan, Abdulmueti Alhadi, Mohammed Abdunaser dra, Nadia M Abdalhamed, Ismail A Saleh, Bashir Abobaker Albakosh, Najat Ben Hasan, Salema S Bin Wali, Hayat Ben Hasan, Hana B Yahya, Marijus Ambrazevicius, Narimantas E Samalavicius, Donatas Venskutonis, Albertas Dauksa, Zilvinas Dambrauskas, Rita Gudaityte, Audrius Dulskas, Gediminas Januška, Kestutis Strupas, Tomas Poskus, Aiste Gulla, Rebecca Caruana, Parth K Patel, Ernest CW Ong, Sarfraz Ahmed, Ahmad Ramzi Yusoff, Bahiyah Abdullah, Mohd Fairudz Mohd Miswan, Sui-Weng Wong, Ruhi Fadzlyana Jailani, Nor A Hakim, Hizami Amin Tai, Lee Fei Yee, Ahmad S Yahaya, Nik Q Fathi, Kelvin Voon, Wei Pin Hung, Ruzaimie Noor, Syahrul Anuar Salleh, Muhamad Izwan Ismail, Tan Jih Huei, Rosnelifaizur bin Ramely, Andee Dzulkarnaen Zakaria, Ikhwan Sani Mohamad, Mohd Nizam Md Hashim, Mohamed Shafi MahboobAli, Norhafiza Ab Rahman, Ahmad Faidzal Othman, Mat Salleh Sarif, Feng Yih Chai, Lim See Liang, Razrim Rahim, Sentilnathan Subramaniam, Jin-Jiun Mah, Firdaus Hayati, Aini Fahriza Ibrahim, Yew Chor Kuan, Hans A Mahendran, Abd Jabar Nazimi, Farrah Hani Imran, Roszalina Ramli, Norshamsiah M Din, Tang Seng Fai, Syed Nabil, Mae-Lynn C Bastion, Ian Chik, Shireen A Nah, Sivakumar Krishnasamy, April C Roslani, Peng Soon Koh, Li Ying Teoh, Mee-Hoong See, WeiJin Wong, Yew Toong Liew, Ahmad N Fadzli, Atif Amin Baig, Francesca Chircop, Kurt Lee Chircop, Josephine Psaila, Guillermo Yanowsky- Reyes, Jaime Orozco-Perez, Rafael Santana-Ortiz, Laura G Peña-Balboa, Sergio A Trujillo-Ponce, Raúl A Miranda, Luis A Lara, Jose-Luis Beristain-Hernandez, Juan Roberto Torres Cisneros, Sonia López, Ricardo Arceo-Olaiz, Ernesto Anaya, Francisco J Ochoa C, Bernardo J Gutierreaz-Sougarret, Christian E Soulé-Martínez, Arianne I Lupián-Angulo, Enrique A Sanchez-Valdivieso, Mónica Noguez-Castillo, Dorihela Herappe Mellado, Roberto A Núñez González, José A Ortega Jiménez, José V Pérez-Navarro, Alejandro González-Ojeda, Francisco J Barbosa-Camacho, Paola Flores-Becerril, Isaac Esparza-Estrada, Jose A Guzman-Barba, Emilio A Reyes-Elizalde, Aldo Bernal-Hernandez, Juan C Ibarrola-Peña, Ruben E Moran-Galaviz, Luis R Pacheco-Vallejo, Bertha G Guzmán-Ramírez, Guadalupe Castillo-Cardiel, Luis RRamirez-González, Luis H Govea-Camacho, Antonio Ramos-De La Medina, Mario Trejo-Avila, Erik E Sosa Duran, Victor M Pinto Angulo, Victor Visag-Castillo, Angélica A Soto-Carvajal, Aldo F Izaguirre, Gustavo Martinez-Mier, Luis Hernández Miguelena, Edgard Efren Lozada Hernandez, Francisco Cesar Becerra García, Javier Melchor-Ruan, Noel Salgado-Nesme, Daniel Garay-Lechuga, Omar Vergara-Fernandez, Gabriela Ambriz-González, Alberto N Peón, Alejandro Durán-Méndez, Eduardo N Ortega, Daniela Pérez, Gustavo Salgado-Garza, H Alejandro Rodriguez, Gheorghe A Rojnoveanu, Marin G Vozian, Radu I Gurghis, Petru Caraja, Sarnai Erdene, Erdene Sandag, Soyombo Orsoo, Sergelen Orgoi, Asmae Kinany, Youness Bakali, Slaoui Aziz, Walid Bijou, Hasnae Guechati, Lina Boualila, Bouanani Othmane, Taha I Sefrioui, Rajaa B El Azzouzi, Mohammed Yassaad Oudrhiri, Hajar Bechri, Abdelghafour Elkoundi, Amine Souadka, Amine Benkabbou, Mohammed Anass Majbar, Nezha ElBahaoui, Raouf Mohsine, Ghita El Mohafide, Brahim El Ahmadi, Abdelilah Ghannam, Zakaria Houssain Belkhadir, Anadi Khatri, Prashant Tripathi, Subarna Bhusal, Sunil Munakomi, Frank W Bloemers, Roel Bakx, Mark I van Berge Henegouwen, Suzanne S Gisbertz, Ben FJ Goudsmit, Wouter KG Leclercq, Louisa N Spaans, Niels J Harlaar, Schelto Kruijff, Gabriela A Sansoni, Netanja I Harlianto, Joop L Konsten, Frank C den Boer, Nicole AM Dekker, Donald Schweitzer, Michael JJ Chu, Natalie Allen, Jim Hsu-Shun Wang, Oliver Lyons, Fiona J Carey, Deborah M Wright, Nicholas J Lightfoot, Tiffany C Oliver, Daniel D Wen, Vidit Singh, David C Kieser, Nichola C Wilson, Chris Varghese, Paul V B Fagan, Matthew James McGuinness, Christopher Harmston, Néstor Javier Pavón Gómez, Harissou Adamou, Abdullahi M Kirfi, Dr Mohammed M Abdull, Auwal Adamu, Haruna U Liman, Bello Shahir Umar, Ademola Adeyeye, Oghenekaro S Ifoto, Akinola Akinmade, Keffi Mubarak Musa, Nasir Oyelowo, Musliu Adetola Tolani, Tunde Talib Sholadoye, Alfa Yakubu, Okeoghene M Ajagha, Lovely Fidelis, Oluseyi O Ogunsua, Muhammad Daniyan, Jameel I Ahmad, Ibrahim U Garzali, Musbahu S Kurawa, Mohammad A Mohammad, Sadiq Hassan, Saminu Muhammad, Lawal B Abdullah, Idris U Takai, Mohammed S Aliyu, Saudat G Habib, Misbahu H Ahmad, Sani A Aji, Abdulrazak Ajiya, Collins C Adumah, Omotayo F Salami, Amina Mohammed-Durosinlorun, Stephen Akau Kache, Matthew C Taingson, Joel Amwe Adze, Olajide O Abiola, Julius G Olaogun, Oluwatosin A Akinruli, Philip O Abolanle, Emmanuel I Eze, Danjuma Sale, Barnabas T Alayande, Christopher N Ekwunife, Chukwuma E Okereke, Chinwendum U Ekpemiro, Akinwale Ibrahim Afolabi, Oluniyi O Olubayo, Oluwasuyi E Ige, Olaolu O Adebayo, Ademola T Adebanjo, Ngozi Nwahiri, Abiodun Idowu Okunlola, Olakunle F Babalola, Owolabi D Ojo, Ojo D Dele, Idowu Adebara, Tesleem O Orewole, Paul O Abiola, Abiyere O Henry, Ifeanyichukwu M Chukwu, Olufemi E Idowu, Iloba G Njokanma, Olabamidele A Ayodele, Omolara M Williams, Omolara M Faboya, Thomas Olagboyega Olajide, Ahmed A Salawu, Aloy Okechukwu Ugwu, Justina O Seyi-Olajide, Oluwaseun A Ladipo-Ajayi, Orimisan Belie, Taopheeq B Rabiu, Oluwole Olayemi Olaomi, Onyedika G Okoye, Soliudeen A Arojuraye, Gbenga E Jones, Okechukwu H Ekwunife, Ochonma A Egwuonwu, Chiemelu D Emegoakor, Victor I Modekwe, Olugbenga O Ojo, Simon A Balogun, Temitope O Ajekwu, Henry E Omon, Christopher O Anele, Abdulhafiz O Adesunkanmi, Omotade A Ijarotimi, Edward O Komolafe, Samuel C Ajekwu, Adewale O Adisa, Funmilola O Wuraola, Adebayo M Olugbami, Adewale A Aderounmu, Olubukola O Allen, Akeem A Adeleke, Adedayo O Lawal, Fayowole O Nana, Oluwatoyin O Fadare, Mohammed Maigana, Akaninyene E Ubom, Tajudeen O Mohammed, Amos O Adeleye, Lateef A Baiyewu, James A Balogun, Akinyinka O Omigbodun, Timothy O Aladelusi, Ebere O Ugwu, Oluwole A Ogundoyin, Afieharo I Michael, Tolulope O Ogunrewo, Oluwabukade T Ojediran, Ifeanyichukwu K Egbuchulem, Nelson U Okoh, Olakayode O Ogundoyin, Olubunmi E Odeyemi, James O Eyitayo, Olayinka A Olawoye, Taiwo A Lawal, Olumide D Akinmoju, Rukiyat A Abdus-Salam, Constantine Ezeme, Shekinah Y Williams, Ajibola B Oladiran, Samuel T Oladejo, Izegaegbe O Obadan, Goodluck A Nwachukwu, Samuel A Ademola, Ikechukwu B Ulasi, Chiedozie K A Ikwu, Folake B Lawal, Oghenekevwe E Okere, Adefemi O Afolabi, Olukayode O Abayomi, Olalere O Gbolahan, Adegbolahan J Fakoya, Adebolajo A Adeyemo, Ogunkeyede S Ayodeji, Habiba I Abdullahi, Samuel A Sani, Stephen E Garba, Bilal Sulaiman, Samson Olori, Godwin O Akaba, Esezobor P Egbor, Emeka D Odai, Michael C Ezeanochie, Omorodion O Irowa, Peter I Agbonrofo, Amina L Okhakhu, Ngozi C Onyeagwara, Nnamdi J Nwashilli, Ekene V Ezenwa, Chidiebere Peter Echieh, Hadijat O Raji, Jibril O Bello, Abdulrasheed A Nasir, Lukman O Abdur-Rahman, Ademola A Popoola, Felix O Kumolalo, Uchechukwu O Ezomike, Ndubuisi O Onyemaechi, Bolaji A Akanni, Vincent Chidi Enemuo, Ikechukwu A Nwafor, Ugochukwu U Nnadozie, Aloy Okechukwu Ugwu, Rosemary N Ogu, John I Ikimalo, Kelechi E Okonta, Dabota Y Buowari, Knut Magne Augestad, Gurpreet Singh Banipal, John Massoud, Amur Al Ismaili, Zainab Nasser Al Balushi, Mustafa M Alward, Hilal A Al Sabti, Abdullah S Al-Mujaini, Dhruva Nath Ghosh, Farman Ali, Bashar A Dawud, Sareyah AlSibai, Russell S Martins, Lubna M Vohra, Shoaib Muhammad, Azza Sarfraz, M Tayyab H Siddiqui, Arsalan Pervaiz, Sakina S Abidi, Pawan K Thada, Sidra Aleem, Saud J Choudhry, Eesha Yaqoob, Asad A Kerawala, Muhammad H Chaudhary, Muhmmad A Chaudhary, Mujahid Z Ali, Imran Mazhar, Omer B Khalid, Nabila Kausar, Muhammad I Khokhar, Allah Nawaz, Muhammad U Malik, Adam U A Butt, Abdur Rehman, Muhammad A Ghufran, Lajpat Rai, Sajida Qureshi, Summaya Saeed, Aafia Maqsood, Khursheed A Samo, Zouina Sarfraz, Manahil Jamil, Saad Javed, Tayyab M Khan, Muhammad S Khan, Areeb Khalid, Shahzad A Khan, Ayesha Javed, Muhammad M Khan, Faiqa Zaki, Sajid Malik, Shahneela Manzoor, Mariyah Anwer, Waleed Mabood, Mohammad S Aaghar, Qasim Mehmood, Hassan Waqar, Azwa Janjua, Sobia Manzoor, Ehsan A Khan, Sajeela Murtaza, Muhammad A Anjum, Muhammad S Farooq, Muhammad K Munir, Muhammad S Akhtar, Syed I Bukhari, Shams U Rehman, Faaiz A Shah, Awais A Malik, Shamail A Syed, Imad-ud-din Saqib, Hassan Mushtaq, Kashif Z Mahesar, Muhammad Tariq, Aun Ali, Raza Sayyed, Asrar Ahmad, Noor U H Maria, Ayesha Iqbal, Abdul Rehman, Ahmad U Qureshi, Usman I Butt, Adeel Islam, Rana Danish, Ammar Waqas, Munaza A Javed, Dur-e Zahra, Saqib Ali, Haroon J Majid, Ahsan Irshad, Muhammad A Naseer, Irfan I Nasir, Ali H Bangash, Humera N Altaf, Syed M A Bukhari, Jehangir F Ali, Muhammad Asif, Samiullah K Niazi, Warda Tahir, Muhammad U Aziz, Nabila Talat, Tanwir Khaliq, Abeer Irshad, Muhammad F Ahsan, Shahzad H Waqar, Fatima Mustafa, Mohamad A Banat, Baha G Albaradiyyah, Farah Bilal Shahin, Hamdoon Abu-Arish, Rami A Misk, Rawand Titi, Khalil N Abuzaina, Bashar Y Awad, Mohammad Y Awad, Roa'a M Aljunaidi, Asala Khalil Hasani, Bushra K Pujee, Malak Y Jibreel, Orwa M Abusabha, Saja E Abusabha, Haneen I Eid, Abdalqader A K Wishah, Abdallah Ibrahim AbuJlambo, Mahran Daowd Darweesh, Ameer kh Shehada, Mohammed I Altallaa, Momin M Y Hilles, Abdallah M Alwali, Sewar A Elejla, Ayat A Aljuba, Mahmood R Manasra, Hadeel I Awad, Sajeda y Karkour, Amal M Shawabka, Bara M AbuIrayyeh, Omar A Mousa, Sarah Amro, Fatima I Aburayyan, Tareq Z Alzughayyar, Jihad S Zalloum, Hamdoon J Abu-Arish, Fida K Hussien-Al-Ali, Tamer S Asafrah, Sami D Jabari, Omar Q Heih, Rahaf Haitham Muhtaseb, Malak Y Jibreel, Asala K Hasani, Omar Khaled Alsarahna, Abdelrahman M Alwali, Ahmed Hassan Albelbeisi, Mustafa A Abu Jayyab, Omar H Salloum, Adalberto Yangüez, Reinaldo Isaacs Beron, Mariela G Hurtado, Hugo A Gomez, Fanny Corrales, Kiichiro Matsumura, Alejandro Arévalo, María José Martínez, Brayan D Pedrozo, Rosa I Sánchez, Dulce Añazco, Cristian Chavez, Cesar G Sisa, Herald R Segovia-Lohse, Helmut A Segovia-Lohse, Eduardo R Santacruz, Alejandro G Leiva, Cesar A Cano, Christian M Lozano, Giuliano Borda-Luque, Lucero Torres-Gomez, Ricardo Arones, W Samir Cubas, Carlos J Shiraishi-Zapata, Gian C Mendiola, Joel J Sánchez, Francisco E Berrospi, Glenda M Falcon, Amabelle A Moreno, Aeris Jane D Nacion, Alberto B Roxas, Hazel Z Turingan, Marie Carmela M Lapitan, Claudine Rosario B Lukban, Marie Dione P Sacdalan, Jose Antonio M Salud, Jeryl Anne S R Reyes, Marinelle M Castro, Ron Daniel Rivera, Maymona J Choudry, Noruel Gerard A Salvador, Karol Szyluk, Marcin Bobiński, Karolina Rasoul-Pelińska, Piotr Major, Justyna Rymarowicz, Pawel Miotla, Konrad Futyma, Maciej Walędziak, Sofia G Reis, João T Oliveira, Marisa D Santos, João Rocha-Neves, António Pereira-Neves, Fabio Gomes, Jorge P M Nogueiro, Sara Castanheira Rodrigues, Pedro C Santos, André de Araújo Pereira, Joao Barbosa-Breda, Diogo D Monteiro, Luís Duarte-Gamas, Leandro Nóbrega, Lara R Dias, Carlota Ramos, Rita G Branquinho, Miguel F Cunha, Nelson J Silva, Ana Claudia M Deus, Pedro Azevedo Serralheiro, Ana P Soares, Susana A Henriques, Pedro Botelho, Brigitta Cismasiu, Ana L Barreira, Miguel Ángel Fernández Romero, Paulo Santos-Costa, Cristina Costeira, João M Carvas, Fayez Mohamed Bin Omran, Ejaz A Latif, Ali T Toffaha, Mohammad Sameer, Amjad S Qabbani, Hussam E Elmelliti, Hamzah El Baba, Mohamed T Khalifa, Saif Badran, Mohamed Said Ghali, Maja Konjanoska, Snezhana B Kavain, Biljana Kuzmanovska, Albert Lleshi, Anita Kokareva, Biljana T Kiprijanovska, Vanja Trajkovska, Marta T Nicevska, Aleksandra Gavrilovska-Brzanov, Marjana Burmuzoska, Tatjana Davitkovska, Aleksandra Jakimovski, Filip Kostovski, Biljana Eftimova, Simon Trpeski, Biljana R Korunoska-Merdjanoski, Blagoj T Shuntov, Venko Filipce, Vladimir Rendevski, Anita Fileva, Toni Risteski, Sofija Pejkova, Gordana Georgieva, Blagoja Srbov, Bisera Nikolovska, Stavridis A Sotir, Katerina Kasapinova, Ioan Alexandru Florian, Radu Drasovean, Mihai-Stefan MA Muresan, Florin Grama, Andrei Chitul, Cosmin Bezede, Emilica Ciofic, Daniel Cristian, Elena Adelina Toma, Valentin Calu, Adrian Miron, Octavian Enciu, Ionut Negoi, Ionut Bogdan Diaconescu, Bogdan Stoica, Mihai G Stefan, Liana Valeanu, Raluca Bievel Radulescu, Nicolae Gh Bacalbasa, Natalia Motas, Madalina C Iliescu, Veronica Manolache, Mihnea Davidescu, Andreea-Madalina Serban, Sebastian N Ionescu, Eduard-Alexandru Bonci, Andrei Pasca, Roxana A Coman, Ioan-Catalin Vlad, Sorinel Lunca, Ana-Maria Musina, Natalia Velenciuc, Gabriel Dimofte, Octav Ginghina, Radu Mirica, Razvan Iosifescu, Andrei B Vacarasu, Mara Mardare, Andrada Spanu, Silviu-Tiberiu Makkai-Popa, Vlad V Porumb, Stelian S Mogoanta, Narcis O Zarnescu, Radu V Costea, Eugenia C Zarnescu, Ayrat Kaldarov, Vasily I Kaleda, Tatiana A Kremenchugskaya, Sergey K Efetov, Vladimir V Balaban, Andrey Litvin, Nikita N Burlov, Gleb Khrykov, Aleksandr G Butyrskii, Khasan E Dzhumabaev, Igor V Pravosudov, Pavel A Ermolaev, Arkady L Bedzhanyan, Yulia V Frolova, Yurii Kudryavcev, Konstantin Kim, Tatyana Mikhaylova, Vyacheslav Ten, Alexey Yanishev, Anastasia Novikova, Rostislav Pavlov, Gleb Kim, Dmitry Shmatov, Maxim Stolyarov, Evgeniy S Drozdov, Petr Mikhailovich Chavkin, Mahir Gachabayov, Irénée Niyongombwa, Stephen P Bennett, Christophe Mpirimbanyi, Jean Bosco Katabogama, Hirwa Aime Dieudonne, Ainhoa Costas-Chavarri, Fidele Byiringiro, Eugene Muneza, Nzabamwita Liliane, Kubwimana Olivier, Severien Muneza, Lee-Min Lai, Alshahrani Mushabab Ali, Saeed Baradwan, Mohammad K Alam, Nasser A N Alzerwi, Arif Hussain, Umar Rahim Bakhsh, Abdullah Alkhayal, Mohammed H Alnasser, Rajkumar Rajendram, Yadullah Syed, Hattan F Dagestani, Abdullah T Eissa, Munira A Al Suwailem, Ali H Farsi, Deema Farsi, Nadim Malibary, Abdulmalik Altaf, Mohammed Basendowah, Saleh S Baeesa, Nouf Y Akeel, Nora Hatem Trabulsi, Abdullah M Bahakim, Khalid Bajunaid, Mohammed H Bangash, Mohammed Alharthi, Murad Aljiffry, Abdulrahman J Sabbagh, Nasir M Bustangi, Basmah S Altuwayjiri, Amani m Alhaddad, Mohammed A Ghunaim, Ali A Samkari, Mohammed A Elzain, Ahmed Y AlAmeer, Dauda Bawa, Hadeel A Ghunaim, Abdulrhman A Ghunaim, Hind Waleen M Mousa, Abdulrhman Saleh Almulhim, Abdulaziz M Alshammari, Mohammed Abuzaid, Emad J Al Absi, Mohammed Abdulrazzaq Al Duhileb, Al Duhileb, Nora E Almana, Ali A Alzahir, Fozan Abdulqader Aldulaijan, Tariq Madkhali, Turki F Alshammari, Bikheet Moh Almatar, Salman Mufareh Ghazwani, Amal A Hamid, Soliman F Ghedan, Amal Alhefdhi, Osama Alomar, Ismail Al-Badawi, Hani Salem, Ahmed Abu-Zaid, Ahmed Nazer, Ahmad K Alnemare, Musaed F Rayzah, Ahmed M Alzahrani, Saad M Alqahtani, Anas A Hasson Alnajjar, Mohammad Alyami, Amar Faisal Elawad, Mashhour H Alqannas, Delia Cortes-Guiral, Yousef S Alalawi, Ahmad S Alayed, Youssef A Alishi, Sharfuddin Chowdhury, Raed Almannie, Thamer Nouh, Mohammed N AlAli, Ahmad M Almalki, Kaleem Ahmed, Abdullah E Kattan, Abdu Hasan Ayoub, Eyad I Al-Kharashi, Fahad Khalid Aljaber, Abdullah H Alghamdi, Ibrahim Al Hasan, Fatima Ahmed Badahdah, Jubran J Al Faifi, Abdullah A Albarrak, Abdou Niasse, Abdourahmane Ndong, Nikola Slijepcevic, Ivan Paunovic, Vladan Zivaljevic, Stefan Kmezic, Aleksandar M Sekulic, Jelenko R Jelenkovic, Ivan B Dimitrijevic, Goran I Barisic, Marko M Miladinov, Zeljko Z Grubac, Boris S Tadic, Nikola Grubor, Ivana Pavlovic, Milorad Reljic, Milica D Mitrovic, Dusan Micic, Zlatibor Loncar, Pavle Gregoric, Aleksandar Karanikolic, Milan D Perovic, Drago Jelovac, Rosanda V Ilic, Aleksandar D Miljković, Ivan Bogdanovic, Ana D Jotic, Lazar Davidovic, Uros Bumbasirevic, Nebojša J Prijović, Veljko Santric, Branko M Stankovic, Dejan D Stevanovic, Aleksandar V Lazic, Nebojsa D Mitrovic, Dragana D Zivkovic, Ivan Z Markovic, Marko N Buta, Merima R Goran, Dragana R Radovanovic, Zoran Radovanovic, Sanja Zahorjanski, Aleksandar Djermanovic Mladjan Protic, Milana Kresoja-Ignjatović, Mladen Djurić, Mikan R Lazovic, Sinisa V Ducic, Bojan M Kovacevic, Jovana M Bojicic, Jovan T Juloski, Igor Krdzic, Vladan Z Milutinovic, Chi Wei Mok, Doris Mae Dimatatac, Ker-Kan Tan, Bettina Lieske, Shuxun Lin, Han Boon Oh, Sabrina Ngaserin, Frederick H Koh, Faith Qi Hui Leong, Tousif Kabir, Jeffrey J Leow, Ming Ngan Aloysius Tan, Wei-Wen Ang, Vishal G Shelat, Radoslav MorochoviÄ, Kristián šimko, Ladislav Czako, Branislav Gális, Michal Vavro, Bronislava Dvoranová, Marek Soviš, Ivana Vidová, Miran Rems, Jurij A Kosir, Ales Tomazic, Jan Grosek, Tajda Kosir Bozic, Ismail M Hersi, Abdifatah D Ali, Abdisamad A Aidid, Abas A Farah, Asma M sh Ahmed, Vered Lack, Maria Fourtounas, Christo Kloppers, Naser Almgla, Eugenio Panieri, Francois Malherbe, Timothy C Hardcastle, Reinier Swart, Colin B Noel, Asha Franciska Malan, Corné PG Nel, Carolina Lugo, Alfonso Lagares, Cristina Ojeda-Thies, Marta Paniagua García-Señoráns, Vincenzo Vigorita, Laura Rodríguez Fernández, Oscar Cano-Valderrama, Andrea Jiménez Salido, Luis Angel Suarez Gonzalez, Sara Busto Suarez, Mateo Hevia, Mario de Arriba Alonso, Teresa Renedo Villar, Isabel Valentín-Gamazo González, Jacobo Trebol, Miguel Mayo-Yáñez, Cristina Barrena López, Ana Sánchez Mozo, Octavio Arencibia, Daniel Gonzalez Garcia-Cano, Leticia Gómez Viana, Ladislao Cayetano Paniagua, Carolina Martinez-Perez, Antonio Melero Abellán, Carolina S Romero, Juan C Catalá, Bernardo Núñez-García, Antonio Gimenez Gaibar, Natalia Álvarez García, Josep M Muñoz Vives, Aránzazu Calero-Lillo, José M Villacampa, Víctor Domínguez-Prieto, Virginia Jiménez Carneros, Laura Alonso-Lamberti, Alba Manuel-Vazquez, Ainhoa Valle Rubio, Julio Domenech, Ignacio Miranda, Hanna Perez Chrzanowska, Lucila Marquez, Albert Baduell, Mariano Balaguer-Castro, Pilar Camacho Carrasco, Marina Cámara Vallejo, Borja Campuzano Bitterling, Anna Carreras-Castañer, Guillem Claret, Francisco J Cuesta-González, Alberto Di Somma, Joaquim Enseñat Nora, Neus Fabregas, Ada Ferrer Fuertes, Abel Ferrés, Cesar Ginesta, Jose J Gonzalez Sanchez, Isabel Gracia, Jhon A Hoyos Castro, Montsant Jornet-Gibert, Xavier Morales, Alejandra Mosteiro-Cadaval, Leire Pedrosa, José Poblete Carrizo, Marina Renau-Cerrillo, Luis A Reyes Figueroa, Pedro Roldan Ramos, Jordi Rumià Arboix, Marta Sabater-Martos, Ramon Sieira-Gil, Thomaz E Topczewski, Jorge Torales, Ramon Torné, Pere Torner, Victor Turrado-Rodriguez, Ricard Valero, Marian Vives-Barquiel, Marta Suñer Campanales, Raúl Jiménez Aguilar, Adriana Bravo, Sergio Giles, Daniel Martín Barreda, Marc Ferrer, Lorena Gómez López, Maria F Peraza Godoy, Roger Pujol Muncunill, David Gutierrez Medina, Yury Postnikov, Alfonso Alías Petralanda, Montserrat Monfort-Mira, Xavier Carreras-Castañer, Luis J Ramirez, Alba Torroella-Vallejo, Borja de Lacy, Clara Chimeno Pigrau, Eloy García Diez, Carles Martí Pagès, Rocío Gallego Sobrino, Caribay Vargas, Érica A Segura Nebot, Jesús D Narvaez, Oscar Ares, Alonso Zumbado, Salvador E Madariaga, Maria M Llompart Coll, Leticia Torres Iñiguez, Carolina González, Justo Gómez, Paula Dominguez, Carolina Montoya, Mariona Balart, Miguel del Pino, Oscar García Lillo, Ricardo Ostilla, Saúl Palomino-Chulla, Manuel López-Baamonde, Barbara Burgos-Blasco, Jana Dziakova, Jaime Rodriguez de Alarcon, Beatriz Vidal-Villegas, Ignacio Cristóbal, Jose M Martinez-de-la-Casa, Rafael Badenes, David Moro-Valdezate, Beatriz De Andrés-Asenjo, Juan Bustamante-Munguira, Héctor J Aguado, Nuria Ruiz-Lopez, Adela Pereda-Manso, Yolanda Carrascal, María Bragado González, Elvira Mateos Álvarez, Juan Berrocal Cuadrado, Sergio Chávez Valladares, Bárbara Segura Méndez, Clarisa Simon-Perez, Virginia Garcia-Virto, Begoña A Alvarez-Ramos, M Carmen Cervera, María Plata, Ana Zabalza, Gregorio de J Labrador Hernández, Jeancarlos Trujillo-Díaz, Dolores Arribas, Giulia Vitiello, Santiago Sánchez-Cabús, Heura Llaquet-Bayo, Cristina Martin-Villares, Ana Minaya-Bravo, Manuel Medina, Enrique Gonzalez, Ana Sánchez-Gollarte, Armando Galvan Perez, Miguel Ruiz Marín, Emny R Bobadilla Romero, Milagros Carrasco Prats, Clara Giménez-Francés, Rebeca Gonzalez, Marta M Arroyo-Domingo, Jesús A Marínez-Alonso, Alejandra Jara Maquilón, Laura Guillamon-Vivancos, Ana Isabel Avellaneda Camarena, Alfonso Capitan, Enrique Viviente Rodriguez, Alfonso Marco-Garrido, Marta Roldón Golet, Mercedes Estaire-Gómez, Francisco Javier Redondo Calvo, Luis Sánchez-Guillén, Álvaro Soler-Silva, Olga Mateo-Sierra, Begoña Quintana-Villamandos, Manuel Tousidonis, Florencio M Marin, Pablo Rodriguez Garcia, Miguel A Freiria Eiras, Marc Vallve-Bernal, Silvia Bleda, Joaquin De Haro, Paula Troncoso, Juan C Martín del Olmo, Juan R Gómez-López, Melody García Domínguez, Jose M Morales-Puebla, Isabel López-García, Jorge Escartin, Issa Talal El-Abur, David García Aguilera, Oriol Martin-Sole, Sonia Pérez-Bertólez, Irene de Haro Jorge, Oscar Izquierdo Corres, Ismael Mora-Guzmán, Jose R Oliver Guillen, Alina Lopez de-Fernandez, Beatriz Fernandez-Velilla San-Jose, David Julià Bergkvist, Laura Ruiz-Villa, Eduardo González Marín, Alba Vázquez Melero, Lorena Varela, Mikel Prieto Calvo, Ibabe Villalabeitia Ateca, Arkaitz Perfecto, Patricia Alonso Carnicero, Elena Aranda, Patricia Martin-Playa, Leire Aparicio Elizalde, Yaiza Galvañ, Julio Plata-Bello, June Fernández-Fernández, Aida C Rahy-Martín, Clara Rosas-Bermúdez, Maria Pelloni, Marcello Di Martino, Jorge Prada Pendolero, David Díaz Pérez, Manuel Losada, María García-Conde, Beatriz Diéguez, Miguel Hernandez-Garcia, Francisco Ripoll Vidal, Jon Zabaleta, Alvaro Sánchez Barrueco, Pablo Beltran-Miranda, Jose M Morales-Puebla, Jenny Guevara-Martínez, Pablo C Arteaga Asensio, Sef Saudí, Ursula M Jariod-Ferrer, Maria V Duque-Mallén, Miguel A Dobon, Carlos Gracia-Roche, Fernando Mendoza-Moreno, Nelson Morales Palacios, Manuel Diez-Alonso, Belen Matías-García, Lucía Diego, Alma Blázquez-Martin, Patricia Burgos-Blasco, Diego Ramos, Emilio Berna-Rico, Luis Ley, Fátima Sánchez-Fernández, Laura Del Río-Arroyo, Rafael Barberá, Alberto Cabañero Sánchez, Alberto G Barranquero, Lourdes Montes-Jovellar, Francisco J Tejero-Pintor, Javier Mata Estévez, Enrique Colás-Ruiz, Beatriz Gomez-Perez, Joaquin Moya-Angeler, Ana Delegido, Pedro José Gil Vázquez, Felipe Alconchel, Vicente J León-Muñoz, Tatiana Nicolás López, Jose Pintor-Tortolero, Luis Tallon-Aguilar, Sandra Dios-Barbeito, Luis C Capitán, Juan-Carlos Gomez-Rosado, Luis C Capitán-Morales, Aitor Landaluce-Olavarria, Javier Ripollés-Melchor, Ane Abad-Motos, Elena Sáez-Ruiz, Alicia Ruiz-de-la-Hermosa, Antonio Perez-Ferrer, Manuel Moriche-Carretero, Remedios Revilla-Amores, Daniel Serralta de Colsa, Benito Alcaide, Rubén Martín-Láez, Emiliano Cano-Trigueros, Víctor Soria-Aledo, Nuria Aguado, Juan J Segura-Sampedro, Susana González-Suárez, Martin Espinosa-Bravo, Jorge H Nuñez, Ramon Vilallonga, Antonio Gil-Moreno, Daniel Gil-Sala, Eloy Espin-Basany, Ruth Blanco-Colino, Manuel Lopez, Jacob Motos Micó, Oshan Basnayake, Umesh Jayarajah, Naveen S Wijekoon, Indu A Jayawardane, Duminda Subasinghe, Sanjeewa A Seneviratne, Dakshitha P Wickramasinghe, Pramodh Chandrasinghe, Sujeewa PBThalgaspitiya, Anuradha B Jayathilake, Wasantha Wijenayake, Israa A Omer, Eman Elsadig Mustafa, AlQasim Mohammed Ahmed Abdallah, Ali A Ali, Ghalib N El Hunjul, Deema Mohamedfagir Osman Mukhtar, Mustafa Mohamed Ali Hussein, Abdoalsalam Shogar, Muneeb E Abdallah, Abdalkader Shaar, Mohamed Nafea shaar, Mohamad khaled kora, Khadija Ala Muhmmed, Monira Mohammed Sarih, Mohammed E A Omer, Moyasar A Idris, Osama S Osman, Elharith MA Alawad, Mustafa Abdalla Bakhit Ebad, Ahmed M Ibrahim, Khider Altayeb Bakheet Abass, Alshareef Bakri Yousif Mohamed Nour, Hytham K S Hamid, Khabab Abbasher Hussien Mohamed Ahmed, Mohja Elsheikh Obeid Ibrahim, Abubaker M Yassin, Salma Esam Mohamed Elhassan Abdelrahman, Adnan Ayman Alnaser, Tarig M Taha, Mohammed E A E Adam, Abdelkareem AAhmed, Mustafa Abdalla bakhit Ebad, Mohammed Ahmed Idrees Saadelnour, Ali Mohamed Ahmed Adlan, Azzain Ismail, Elmustafa Alkhalifa, Ibrahim Ali Mohamed Abdalaal, Tarig Fadalla, Mohamed Yahia Ibrahim, Elaf A Hamdoun Aziz, Muhsin Mohammed E A Mohammed, Tasneem A Mohamed, Ali Alsaeed Ali Alhag, Rayan Ibrahim Hamid Mohamed, Salih Boushra Hamza, Mohamed Abdelazim Mohamed Ali, Nidal Youseef A A Ahmed, Albrra Alhag Mohamed Alhag, Mahmoud Saleh, Elmustafa Alkhalifa, Monir Jawad, Anders Thorell, Josefin Segelman, Rebecka Hultgren, Peter Elbe, Michelle S Chew, Shahin Mohseni, Pamela Buchwald, Andreas Älgå, Gabriel Sandblom, Martin Nordberg, Malin Sund, Martin Rutegård, Maziar Nikberg, Francesco Mongelli, Matteo Di Giuseppe, Andrea Papadia, Maria Luisa Gasparri, Morena Antonilli, Sotirios-Georgios Popeskou, Nicola Colucci, Eleftherios Gialamas, Oliver Dwidar, Marc-Olivier Sauvain, Christine F Maurus, Gregor J Kocher, Lukas W Widmer, Simon A Mueller, Roland Giger, Sara-Lynn Hool, Michel Adamina, Georgios Peros, Merima Misirlic, T Bächler, Daniel Schöni, Anas Taha, Jörn-Markus Gass, Thomas Giesen, Daniel Gero, Silvio Däster, Savas D Soysal, Stephanie Taha-Mehlitz, Athanasios Tampakis, Gabriel F Hess, Fabio Nocera, Otto Kollmar, Martin Bolli, Mazen A Mohammad, Anas M Bakdash, Ramez KH Aljasem, Amer A Rahhal, Mohamad A Shareeda, Anas O Nyno, Mahran Adnan kahawati, Bassiel Alchiekh Yassien, Bayan Alsaid, Reham M Bnayan, Basel S Kouz, Mohammad Eyad Takahji, Zein Fouad Hasan, Aalaa Abduljalil, Nawras MAlhalabi, Mohamad Basher A Al Jammal, Diana N Alia, Muhannad Homsi, Joseph Masri, Ruqaya J Masri, Tayf Toutounji, Marwan Al Aliwy, Nasrullah Kabbani, Lama Kadoura, Dana Sultan, Luma Haj Kassem, Houmam Mohamad Al-Naeb, Maher M Al-Hajjaj, Wael Alkhaleel, Sarya Swed, Mohammad Yusuf Naal, Salim Tfankji, Mohammad Husein Rajab Almohammed, Mohammad Hassan Nabhan, Ahmad Al-Mouakeh, Mahfoud M Najjar, Ahmad Alhashash, Ahmad Ghazal, Mhd Obai Alchallah, Homam Alolabi, Muhammad Omar ElHomsi, Omar Rayes, Weaam K Ezzdean, Antoine Naem, Salma MHD Mazen Al-Houssami, Bardisan S Gawrieh, Alaa Hamdan, Naya Talal Hassan, Ali M Hammed, Elias George Elias, Aline Ali Ahmad, Mohammed Amr Knifaty, Ahmed M Moussa, Iddrisu Baba Yabasin, Jun-Neng Roan, Chao-Jung Shih, Po Chuan Chen, Varut Lohsiriwat, Vorapong Phupong, Suphakarn Techapongsatorn, Avery M Lalchan, Shane Charles, Bouchahda Rim, Malek Bouhani, Montassar Ghalleb, Amine Chamakhi, Amine Sebai, Nesrine Ben hadj dahman, Houssem Ammar, Mohamed Amine Said, Nahla Kechiche, Afag Aghayeva, Onur Dülgeroğlu, Volkan Ozben, Erman Aytac, Deniz Atasoy, Akif Enes Arikan, Halil Kara, Nasuh U Dogan, Asli Bostanci, Murat Turhan, Ozlenen Ozkan, Ersin G Dumlu, Ebru Menekşe, Volkan Oter, Erol Piskin, Ismail Hasirci, Muhammet Kadri Colakoglu, Erdal Birol Bostanci, Yigit Mehmet Ozgun, Behic Girgin, Serap Erel, Sibel Demirel, Özge Yanik, Ibrahim Ethem Gecim, Mehmet Ali Koc, Cihangir Akyol, Volkan Güner, Can Konca, Figen Batioğlu, Musluh Hakseven, Tayfun Toptas, Yener Aydin, Ali B Ulas, Ilker Ince, Yuksel Altinel, Serdar Demirgan, Serhat Meric, Mehmet Salih Sevdi, Candas Ercetin, Sina Ferahman, Husnu Aydin, Ahmet Cem Dural, Nuri A Sahbaz, Omer Yalkin, Murat Sen, Ozgen Isik, Ahmet Tuncay Yilmazlar, Tayfun Bisgin, Banu Yigit, Arda Isik, Sezai Leventoglu, Hüseyin bayhan, Mehmet Z Buldanli, Murat Gultekin, Omer Cennet, Ertekin U Unal, Mehmet Çağlar Çakici, Ayberk Iplikci, Asif Yildirim, Ilker Ozgur, Comert Sen, Muserref B Dincer, Ergin Erginöz, Ahmet Necati Sanli, Akif Turna, Ahmet Askar, Server Sezgin Uludağ, Cem E Guldogan, Mehmet M Ozmen, Mehmet A Bozkurt, Adem özcan, Yasin Kara, Ali Kocataş, Ali Guner, Ramazan Sari, Ecem Memisoglu, Kemal T Saracoglu, Yasin Tosun, Kenan Çetin, Erkan Kalafat, Cagatay Taskiran, Dogan Vatansever, Burak Giray, Ozan C Tatar, Hande Köksal, Mehmet Serkan Özkent, Mehmet E Ulutaş, Mustafa B Hamarat, Bora Coskun, Aykhan Abbasov, Ezgi Altinsoy, Tevfik Kivilcim Uprak, Ayten Saracoglu, M Umit Ugurlu, Emin Kose, Utku Ozgen, Ugur Sungurtekin, Emre Gonullu, Zulfu Bayhan, Emrah Akin, Baris Mantoglu, Elif Colak, Gultekin Ozan Kucuk, Cemil Yuksel, Ferit Aydin, Lutfi Dogan, Serdar Culcu, Aydin Eray Tufan, Bulent Citgez, Göksever Akpinar, Ülkü C Köksoy, Hanife Seyda Ulgur, Murat Kalin, Omer Faruk Ozkan, Muhammed Kadir Yildirak, Semra Demirli Atici, Semra Salimoğlu, Burcin Abud, Bulent Calik, Erdinc Kamer, Eyup Kebabci, Ufuk Uylas, Kenan Teker, Guldeniz Karadeniz Cakmak, Fatma Ayca Gultekin, Okedi Francis Xaviour, Otolia Isaac, Turinawe Gaston, Daniel Asiimwe, Bienfait Mumbere Vahwere, Franck Katembo Sikakulya, Herman Lule, Henry Mark Lugobe, Hervé Monka Lekuya, Christine Namugenyi, Ronald Kiweewa, Muhangi Bosco, Ihor Yovenko, Viacheslav Kopetskyi, Bogdan Maksymenko, Sattar Alshryda, Sabina A Khan, Amit Vasantrao Padvi, Mohamed A Serour, Shamim Ahmad Beigh, Hisham M Elsayed, Awadelkarim O Mohamed, Vikram Somashekhar Basappanavar, Amna S Al-Wandi, Kareem S Khalil, Muhammad Umar Younis, Hayder S Abdulhadi Al Saadi, Ginan K Heidan, Ravi K Trehan, Justin Davies, James Ashcroft, Grant D Stewart, Fanourios Georgiades, Amer J Durrani, Stephen J Price, Kai Yuen Wong, Amit Agrawal, Matthew KT Seah, Marwa M E Saad, Nicholas Segaren, Marios Ghobrial, Anita Balakrishnan, Parto Forouhi, Wasim S Khan, James Wheeler, Andrew G Schache, Dimitrios P Katsikostas, Dimitrios Angelou, Adam J Fell, Rana Madani, Shiva Dindyal, Shaikh S Seraj, Premalatha Sharavanan, Muhammad R Iqbal, Nicholas J Wong, William B Lo, Wai C Soon, Dalia Hammouche, Jonathan DE Lee, Max J Pachl, Dinesh Alexander, Shoaib Ahmad, Hannah L Morley, David Selwyn, Jonathan Wareing, Vlasios Oktseloglou, Peter Bobak, Lisa S Rampersad, Mazin Mohamed, Mandeep Kaur, Antonios Athanasiou, Benjamin P Martin, Tarik S Jichi, Tim JP Batchelor, Sophie Rozwadowski, Sarveen Maniarasu, Parisah K Seyed-Safi, Vladislav Kutuzov, Hemina B Shah, Toby M Noton, Nina Jyne Minette Dela Cruz, Neev Trehan, Evripidis Tokidis, Matthew H V Byrne, Stuart C Winter, Rui Pinto-Lopes, Aswathy Pavithran, Ahmad O Khalifa, Nicola J Eardley, Rami Ashour, Jacqueline D Steinke, Husayn D Esmail, Matthew N Bence, Samuel T Walters, Tosin O Akinyemi, Sathya Lakpriya, Nader N Moawad, Pedram Panahi, Joshua Lau, Stephen McAleer, Adeyinka Laoye, Abdulzahra Abdulsamad Hussain, Muneeb Zafar, Mohammed H Elsheikh, Daniel A Shaerf, Fiammetta Soggiu, Abaris Massoumi, Hemant D Sheth, Fahed Gareb, Mark W Yao, Mubasher A Qamar, Clarissa E H Fang, Michael S Greenhalgh, Alexander Hunt, Emmanuel O Oladeji, Miles W Benjamin, Philip Beak, Fraser J Rae, Joanna M S Aithie, Gareth W J Clarke, Darmarajah Veeramootoo, Alex J Ashman, Ehab E Kahka, Tanvir Rafe, PANNA K PATEL, Hatim Albirnawi, Mark Katory, Ann Fisher, Sunil J Amonkar, Pawan Kumar Dhruva Rao, David J Holroyd, Edward J Caruana, Andreas Gkikas, Lydia S Newton, Alan J B Kirk, Ayesha Khalid, David Ferguson, Paul B Stanier, Vinay Shah, Kariem El-Boghdadly, Alexis M P Schizas, Minahi ilyas, Mark L George, Mothana Gawad, William D Groom, Mohammed Al-Azzawi, Julian CJ Ahluwalia, Prakash P Punjabi, Fang Yi Cheung, Michael D Wilson, Claudia Gabriela Mitrofan, Yogeshkumar Malam, Adam Townson, Mahmoud Loubani, Jih Dar Yau, Kevin Seebah, Enoch F Akowuah, Sreekumari R Pushpoth, Yirupaiahgari KS Viswanath, Kareem ElSanhoury, Misha Chew, Thomas E Walker, Almutasim Billah Elbagir Elhassan, Elizabeth Belcher, Matej Goricar, Hooman Soleymani majd, Dominic Knight, Lamiese Ismail, Chris McKinnon, Mario Ganau, Max Prokopenko, Neel S Doshi, Aikaterina Gkorila, Nomaan A Sheikh, Jessica R Helm, Mei Ken Low, Oluseyi Harold Ogunfusika, George Bisheet, Tariq Alhammali, Ahmed Showki Arnob, Jatinder Singh, Emma L Allde, Sharan H Sambhwani, Manas Dube, Elizabeth H Gemmill, Joby John, Ioannis N Gerogiannis, Mona A A Abuelgasim, Georgina Crate, Thomas J Holme, Anh T V Nguyen, Michael W Ho, Ryckie G Wade, Azar Hussain, Paul Andrzejowski, Eugene Omakobia, Momin Eltayeb, Tsanko P Galabov, Chung Yan Vernon Lee, Anum Nazir, Oliver L Siaw, Robert U Ashford, Alex P Boddy, Christopher D Ashmore, Snehadhar M Shah, Benjamin T V Gowers, Dinesh K Thekkinkattil, Dawit Worku, Sharan H Sambhwani, Amer Harky, Rishi Talwar, Harkiran K Sagoo, Periyathambi S Jambulingam, Christopher J Smart, Daniel T Doherty, Sotiris Mastoridis, Sidharth Kumar, Rana Mahmoud, Francesca Solari, Richard J Egan, Jonathan D Barry, Jo Morrison, Kaveh Davoudi, Marianne Hollyman, Andrew Kelly, Thomas F Badenoch, sanjay pandanaboyana, Rebecca J Critchley, Varun R Sarodaya, Robert J H Sinnerton, Jaiganesh Manickavasagam, Elizabeth F Lindsay, Ankita Arora, Raashad Hasan, Ignatius Liew, Joshua Ozua, Vasileios Kouritas, Rachael V Collins, George H Lafford, Charlie Moret, Chung Shen Chean, Liam F Horgan, Avinash Aujayeb, Muhammad Harris Siddique, Lalin Navaratne, Sanjeev Kotecha, Vittoria Bellato, Sophia E Lewis, Muhammad Usman Ali, Ben A Marson, Simon Craxford, Ketankumar Gajjar, Elena Theophilidou, Tariq Aboelmagd, Harman Khatkar, Mario Ganau, Mahmoud A Awadallah, Jose A Blanco, Tsitsi G Chituku, Oliver GB Dixon, Janahan sarveswaran, Imogen S Jones, Salah Hammouche, Vardhini Vijay, Rucira Ooi, Rahi Karmarkar, Tahir Khaleeq, Mohit Bhatia, Badr L Al-Khazaali, Audrina Daadipour, Ahmed Mattar, Tarun Singhal, Moustafa Ibrahim Mahmoud, James Glasbey, Paul C Nankivell, Maninder S Kalkat, Shahd Nour, Andrew D Beggs, Danylo Y Yershov, Shafiq Ahmad Chughtai, Hesham Youssef, Alan R Norrish, Mohammed M Mohammed, Adam M Gwozdz, Michalis P Charalambous, Stephen R Knight, James A McCaul, Elsie A Bridgman, Mustafa El Sheikh, Akinsola Ogunbowale, Evan O Wright, Usama Ahmed, Hafsa Younus, Laura G Tincknell, Ken Weixing-Ho, Charis Demetriou, Mohammed Hussei, John-Joe Reilly, Anil P Hormis, Susan J Moug, Fitzgerald C Anazor, Edward A Horwell, Gregory Neal-Smith, John M McNamara, Kwaku W Baryeh, Khalid M Bhatti, Joseph E McKay, Maria G Cannoletta, Clare J Perkins, Sivakumar Gopalswamy, Anna F Sheldon, Joseph B John, Mark Mantle, Bogdan Toia, Andrew J Phillips, Waleed Al-Khyatt, Jonathan N Lund, Ahmed Y Ammar, Hans Lederhuber, Guang H Yim, Daniel A Huntley, Ian R Daniels, Joao Valverde, Edward David John Lumley, Thomas J Walton, Dimitri A Raptis, Nikolaos Dimitrokallis, Arjun Nathan, Reza Motallebzadeh, Shihab Chowdhury, Rezwan F A Ahmed, Reza Mirnezami, Tamas Szakmany, Dominic J Knight, Waheeb Al-Azzani, Huw R Davies, Setthasorn Zhi Yang Ooi, Khaing K Oo, Paul S Cullis, Ed Peng, Andreas K Demetriades, Andrew L Tambyraja, Michael TC Poon, Thomas M Drake, Paul M Brennan, Dimitrios Oikonomou, Samuel E Newman, Louise Le Blevec, Mohamed Otify, Peter Szatmary, Bhavesh Devkaran, Dana Sochorova, Catrin Sohrabi, Rajesh Sivaprakasam, Mingzheng Aaron Goh, Kate V Atkinson, Delvene Soares, Daniela Prce, Johnathon P Cann, Amy C Grobbelaar, Rebecca Bradley, Helen J Strauss, Ahmed Taha, Annamaria Minicozzi, Mary L Venn, Bhaskar Thakur, Abdullah Hanoun, Poornanand Goru, Rachel M Baumber, Anshul S Sobti, George WV Cross, Tom Havenhand, George A Antoniou, Govind Singh Chauhan, Ismail Vokshi, Ayesha Mahmud, Erminia Albanese, Daisy Evans, Thumuluru Kavitha Madhuri, Jonathan D Horsnell, Pardis Zalmay, Mazin Mohamed, Angharad J Davies, Firas Aljanadi, Reubendra Jeganathan, Mark Jones, Christos Kakos, Raghavan vidya, Alaa El-Ghobashy, Ahmed M Habib, Jeremy P Reid, Harshadkumar Dhirajlal Rajgor, Omar Ahmed, Graham Branagan, Ali Yasen Y Mohamedahmed, Shahd Nour, Ali Al-Sabbagh, Govind Chetty, Clive J Kelty, Yasin A M EL-Wajeh, James E Tomlinson, John G Edwards, Ola Rominiyi, Saurabh Sinha, Sanad Saad, Banchhita Sahu, Vasileios Charalampakis, Ibrahim Enemosah, Simon J Williams, Hassan N Yaqoob, Edward P Laurent, Joshua L Moreau, Rhiannon Frostick, Hammad Parwaiz, Karim Aboelmagd, Dimitri J Pournaras, Kalina H Hristova, Karthikeyan P Iyengar, Muyed Mohamed, Dmitri Y Artioukh, Sibtain Anwar, Mostafa K A Hussein, Tomisin S Omogbehin, Jonathan B T Herron, Amir Labib, Preemal Patel, Samuel C Marsden, Roshana Mehdian, Gowthanan Santhirakumaran, Jeremy Smelt, Ketan Agarwal, Antonios Athanasiou, Luca Lancerotto, Kapil Sahnan, Joseph Shalhoub, Liam J Donnelly, Simon Erridge, Swathikan Chidambaram, Xun Luo, Sujesh Bansal, Neil AJ Ryan, Alexander C D Smith, Michael Flatman, Imad Wafaie, Muhammad Isfandyar Khan Malik, Ruben P Thumbadoo, Shoaib F Hussain, Christin Henein, Yousif T Hamad, Ajay P Belgaumkar, David C Bosanquet, Angelos G Kolias, David Choi, Hani J Marcus, Hugo RM Layard Horsfall, Danyal Z Khan, Arun Sahni, Christopher P Millward, Luke Render, Adam Truss, Tarek Elmoslemany, Chetan Parmar, Joseph Hanger, Jonathon Sheen, Jaideep S Rait, Jennifer Foreman, Natalie Marzouqa, Andreas Fontalis, Grigorios Voulalas, Ryan Chin Taw CHEONG, Sanjay Dindyal, Sathyaseelan Arumugam, Thomas R W Ward, Alastair S Stephens, Eleftheria Douka, Ayesha Mahmud, Ahmad K Abou-Foul, Siobhan C McKay, Mark O Kitchen, Oliver DJ Rees-Stoner, Supriya Balasubramanya, Muhammad Adeel Akhtar, Andrew J Warwick, Shweta Pawar, Vivek Dubey, Mustafa W Al-Yaseen, Christopher YK Williams, Alexander Laird, Kandaswamy Krishna, Ngozi S Anyaugo, Obafemi K Wuraola, Funlayo Odejinmi, Joanna M Craven, Charlotte L West, Reece A Barter, Devaraj M Navaratnam, Shahbaz S Malik, Vimaladhithan Mahendran, Miguel Zilvetti, Richard E Lovegrove, Tim N Board, Moez Zeiton, Safdar A Sarwar, Sarah E Duff, Elmuiz A Hsabo, Poornanand Goru, Ashwani Kumar Nugur, Richard M Morris, Anil K Lala, Rita O Kwan-Feinberg, Samuel W Ross, Jeremy A Dressler, Craig D McClain, Faye M Evans, Shaun E L Wason, Keianna R Vogel, Joanna C Wang, Megan L Sulciner, Sameer Hirji, Mustafa Raoof, Christopher J Wolff, Ilan kent, Alparslan Turan, Pedro G Teixeira, Kristofor A Olson, Neil D Patel, Vijay Krishnamoorthy, Dimitrios Moris, Henry E Rice, Hesham Gabr, Savni R Satoskar, Christine A Castater, Manal Jmaileh, Rachel E Payne, David S Kwon, Shahram Aarabi, Pedro F Escobar, Joshua P Kronenfeld, Michael K Dalton, Eric W Etchill, Elliott R Haut, Dominique Vervoort, Ahmed Dehal, Mark McKenney, Adel Elkbuli, Ankush Gosain, Zaid M Abdelsattar, Matthew R Naunheim, Ciersten A Burks, Allen S Zhou, Marilyn Heng, Shady Abohashem, Santiago A Lozano-Calderón, Janani S Reisenauer, Nicolas J Mouawad, Thomas M Diehl, Evert A Eriksson, Jayson S Marwaha, Thomas J Schroeppel, Christopher J LaRocca, Grace H Chang, Romana Hassan, Lauren B Nosanov, Jennifer L Rickard, Jacob B Avraham, Patrizio Petrone, Joseph J Sferra, Joseph Hadaya, Brittany S Mead, Jason S Hauptman, Maleeha Ahmad, Antonio Meola, Steven D Chang, Ara Ko, Katherine E Specht, Asad Choudhry, Ronald Zerna Encalada, Juan L Poggio, Hang Xing, Nina E Glass, Robert Hooker, Paulo N Martins, Erin M Scott, Brittany K Bankhead, Emmanouil Giorgakis, Joe Nigh, Tamara Osborn, Erika L Tay Lasso, Daniel M Beswick, Allison E Berndtson, Krista L Kaups, Lee-lynn Chen, Michael S Farrell, Marissa A Boeck, Dennis M Vaysburg, Al-Faraaz Kassam, Kevin M Turner, Adam R Dyas, Julia R Coleman, Megan Folsom, Christopher M Lam, Sean C Kumer, Kelsey Larson, Scott Turner, Christopher Guidry, Madhuri Reddy, German Berbel, Austin Findley, David Beahm, Andres Bur, Derek Marlor, Corey Houndschell, Shea Carver, Alissa Ulrich, Neal Bhutiani, Laura DiChiacchio, Hossam Abdou, Lena M Napolitano, Rahel Ghebre, Gary Alan Bass, Lewis J Kaplan, Niels D Martin, Caoimhe C Duffy, Sultan S Abdelhamid, Brian J Daley, Christina L Roland, Ryan P Dumas, Vin Shen Ban, Aashish Rajesh, Mark G Davies, Prabhudev P Purudappa, Camila B Walters, Nicole Lin, Nensi M Ruzgar, Sarah J Ullrich, Ivan Trostchansky, Fernando Bonilla-Cal, Fabiola Castedo, Helena Sobrero, Gastón Acuña, Sofía M Álvarez, Josefina Tarigo, Ana C Carbajal, Ana Carbajal, Antonio R Reyes, Fatima A Al-Eryani, Nardeen N Alqousi, Zainab Alattas, Rafat A Al-Saban, Mohammed M Al-Shehari, Nawal T ALHammadi, Sarah A Shream, Hamza M Al-Naggar, Lina M Al-Qalisi, Areej E Nadeesh, Hytham H Al-Samawi, Hadeel M Bajjah, Saba A AL-Ameri, Jamal F Albably, Rana A Ghannam, Amatallah H Shamsan, Abdullah A Meead, Riham Q Al- Zubaidi, Mohammed A Zulait, Halah Najeeb, Musaed M Alsayadi, Seham K Al-Mashreqi, Najla A Al-Jomai, Ramzi A Alsayadi, Moath M Al-Naggar, Hassan A Almarashi, Hasna M Musaeed, Ibrahim M Al-Raimi, Hossam N Ghanem, Karim A Al-Zazay, Shehab A AL-Mahdi, Amatalaleem S Almontaser, Vanessa A S Savopoulos, James Munthali, Kizito M C Kabongo, Willard Mushiwokufa, Allan Ngulube, Crispin Ntoto, Praise T Magama, Daniel Dzinotyiwei, Shelton K Chivanga, Ngqabutho S Dube, Ernesto C Sanchez, Assel T Moyo, Antony Chengahomwe, Simbarashe Chinyowa, Maphios Siamuchembu, Tafadzwa Bondera, Trust Mushawarima,]